3-OH-FA- and branched GDGT-based temperature calibrations from a transect of lakes in the eastern USA - Changhai Hou; Michael L. Griffiths; Alice Hardman; Osamu Seki; Aifeng Zhou; Sarah Greene; Elizabeth W. Patterson; Roland Indriksons; Sabrina Ryan; Michael DaSilva; Matthew Allison; Lin Chen; et al. (Organic Geochemistry, 2026)

Communication networks of wild zebra finches, Taeniopygia castanotis - K. Hagedoorn; N. Tschirren; E. ter Avest; C. Tyson; L. Snijders; S.C. Griffith; M. Naguib; H. Loning (Animal Behaviour, 2026)

Assessing the vulnerability of elasmobranchs to western and central Pacific tuna fisheries using an improved ecological risk assessment method - Nicholas J. Hill; Shane Griffiths; Valerie Allain; Simon Nicol; Joanne Potts; Naiten Bradley Phillip; Cassandra L. Rigby (Fisheries Research, 2026)

Sharks as apex predators in the Late Cretaceous Western Interior Seaway empirically revealed by zinc isotope analyses - Jeremy McCormack; Harry Maisch IV; Martin A. Becker; Michael L. Griffiths; Jade Knighton; Robert A. Eagle; Kevin Stevens; Wolfgang Müller; Kenshu Shimada (Gondwana Research, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Glare more than uplight attracts flying insects to artificial lights - Brett M. Seymoure; John F. Deitsch; Paul Hyder; Braulio Sanchez; Kajaya Pollard; Isabella Rios; Evan Robinson-Griffiths; Sol Saenz-Arreola; L. Miles Horne; Oceane Da Cunha; Oliver Neria; Joshua J. Mead; et al. (Biological Conservation, 2026)

Biochar reshapes soil bacterial community composition and survival strategies: a meta-analysis revealing trade-offs between microbial stability and functional complexity - Jianwei Li; Jeewani H. Peduruhewa; Robert W. Brown; David R. Chadwick; Robert I. Griffiths; Haoran Fu; Hongfeng Bian; LianXi Sheng; Qinqxu Ma; Davey L. Jones (Biology and Fertility of Soils, 2026)
As a promising strategy for improving soil health and mitigating climate change, biochar has received increasing attention in recent years. However, findings regarding its microbial effects are often context-dependent, and the complex impacts of biochar on soil microbial communities remain inadequately understood. Here, we integrated 843 samples of 16 S rRNA sequencing data from 24 independent studies, utilizing machine learning and co-occurrence network analysis to evaluate general patterns and mechanisms by which biochar alters bacteria community composition and survival strategies. Overall, biochar significantly increased soil organic C, total N, pH, and reduced bulk density, which in turn affected microbial communities. While biochar addition did not notably alter bacterial α-diversity (Shannon index or species richness), it significantly changed β-diversity, indicating that biochar addition altered microbial community composition. Biochar changed community composition and survival strategies by reducing the oligotroph/copiotroph ratio, favouring copiotrophs groups (e.g., Bacteroidota). K -strategists (e.g., Planctomycetota) were reduced by biochar, potentially due to increased nutrient availability and increased competition. Model selection analysis identified that soil physicochemical properties were key drivers of α-diversity, while climate variables were the main factors influencing β-diversity. Biochar properties represented key factors influencing changes in microbial survival strategy. Machine learning identified 138 biomarker genera, with biochar-treated soils showing an increase in Pseudomonadota. Co-occurrence network analysis indicated that biochar increased microbial stability, but reduced network complexity, suggesting a trade-off between resilience and functional redundancy following biochar addition. These findings provide new insights into how biochar influences the composition and ecological functions of soil bacterial communities and offer theoretical support for its scientific application in sustainable soil management.

Quantifying changes in central Vietnam rainfall amount since the Late Pleistocene - Elizabeth W. Patterson; Alliya A. Akhtar; Michael L. Griffiths; David McGee; Quốc Đỗ-Trọng; Annabel Wolf; John A. Higgins; Stefania Gili; Mùi X. Trần; Hùng Q. Nguyễn; Trí H. Đinh; Thành N. Bùi; et al. (Earth and Planetary Science Letters, 2026)

Using pre-release efficacy as a candidate agent prioritisation tool for the weed Trichocereus spachianus (Caryophyllales: Cactaceae) - T. C. Griffith; M. B. Aguirre; G. F. Sutton; L. Chari; I. D. Paterson (BioControl, 2025)
Pre-release efficacy assessments (PREA) can be used to prioritise the most damaging candidate agents for further studies in biological control programmes against invasive alien plants. This study assessed the efficacy of various potential enemies of Trichocereus spachianus (Riccob.) (Caryophyllales: Cactaceae), an invasive cactus in South Africa, in order to prioritise the most damaging candidates for further studies, including host specificity testing. T. spachianus is considered indigenous in Argentina and Bolivia, but the original description was based on a cultivated plant, and it is either very rare or absent in its indigenous range, with no verified records of natural populations. This necessitates the use of new associations collected off close relatives of the target plant as potential biocontrol agents. We evaluated eight potential biocontrol agents by deriving host suitability indices (HSI) and performing efficacy trials. The HSI analysis demonstrated that only one out of the eight candidate agents, a cochineal insect Dactylopius confertus De Lotto (Hemiptera: Dactylopiidae), had high fitness (high survival, fecundity and complete development) on T. spachianus . This helped us eliminate ineffective agents early on in the programme. The cochineal insect was prioritised for efficacy trials, which demonstrated its high potential efficacy, killing approximately 89% of T. spachianus plants over 60 weeks. Taken together, our results indicated that D. confertus is a highly promising potential agent for the biocontrol of T. spachianus in South Africa. By prioritising candidate biocontrol agents based on efficacy prior to host specificity testing, we ensured that the highest priority candidate agent was identified for detailed and resource-intensive host specificity testing.

Telomere length declines with mean blood lead concentration in an urban passerine - Heung Ying Janet Chik; Max M. Gillings; Riccardo Ton; Marco van der Velde; Mark Patrick Taylor; John P. Swaddle; Hannah L. Dugdale; Simon C. Griffith (Environmental Research, 2025)

Preliminary insights into manta ray (Mobula alfredi and M. birostris) population demographics and distribution in South Africa - M. Carpenter; N. Cullain; R. Daly; G. Smith; M. Dicken; V. Dames; C. L. Griffiths; A. D. Marshall (Environmental Biology of Fishes, 2025)
Both the reef manta ray, Mobula alfredi and oceanic manta ray M. birostris , are repeatedly observed in South Africa, yet little is known about the distributions of either species. In this study, we collated citizen science observations since 2003 to reveal six areas in the KwaZulu-Natal (KZN) and Eastern Cape provinces, where manta rays have been sighted across multiple years. Using their unique ventral spot patterning, 184 individuals were photo-identified, comprising 139 M. alfredi and 45 M. birostris . Most of the photo-identified M. alfredi individuals were encountered in the iSimangaliso Wetland Park (IWP) in KZN (89%; n = 119) and for M. birostris , Aliwal Shoal (48%; n = 22). We identified 32 new transboundary records of 28 M. alfredi also photographed in the Inhambane Province, Mozambique, demonstrating connectivity, specifically to Závora ( n = 27). One M. alfredi individual traveled multiple times between the IWP and Závora, Mozambique, totaling 1305 km, and another individual traveled from the Pondoland MPA to the IWP in South Africa, a distance of over 600 km. Further, we extend the southern range for M. alfredi in Africa by over 500 km from Mdumbi Beach to Port Ngqura, Eastern Cape. These collective findings represent South Africa’s first in-water assessment of manta ray aggregations, showing the IWP in particular to be a critical habitat for M. alfredi . Further, the movements documented here suggest the M. alfredi population in southern Africa to be one of the most mobile globally. We hope the baseline data provided here will drive increased research and transboundary management for M. alfredi and M. birostris along the KZN and Eastern Cape coastlines.

Biodegradable mulch films exhibit slower-than-expected degradation with negligible effects on soil microbial communities - Martine Graf; Estelle Choiselat; Michaela K. Reay; Rafael Bargiela; Athanasios Dimitriou; Qiuyun Liu; Robert M. Elias; Peter N. Golyshin; Robert Griffiths; David R. Chadwick; Davey L. Jones (Journal of Hazardous Materials, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Miocene marine vertebrate trophic ecology reveals megatooth sharks as opportunistic supercarnivores - Jeremy McCormack; Iris Feichtinger; Benjamin T. Fuller; Klervia Jaouen; Michael L. Griffiths; Nicolas Bourgon; Harry Maisch; Martin A. Becker; Jürgen Pollerspöck; Oliver Hampe; Gertrud E. Rössner; Alexandre Assemat; et al. (Earth and Planetary Science Letters, 2025)

Maternal Electronic Cigarette Inhalation Exposure During Gestation: Impacts on Prolactin and Xanthine Oxidase - Julie A. Griffith; Kallie J. Schafner; Krista L. Garner; Evan DeVallance; Sara E. Lewis; Timothy R. Nurkiewicz; Eric E. Kelley; Brooke A. Maxwell; William T. Goldsmith; Elizabeth C. Bowdridge (Cardiovascular Toxicology, 2025)

Association between organic micropollutants in tap water and human exposure and birth outcomes: Implications for environmental health in northern Puerto Rico - Yinmei Feng; Justin Manjourides; Stephanie L. Rich; Guangyu Li; Carmen Velez Vega; Ingrid Y. Padilla; Zaira Rosario-Pabón; Akram N. Alshawabkeh; Damian E. Helbling; Griffith Gao; David Kaeli; John D. Meeker; et al. (Journal of Hazardous Materials, 2025)

Policy implications for offshore renewable energy in Australia: An MSP approach supporting the energy transition - Laura L. Griffiths; Camille Goodman; Michelle Voyer; Jackson Stockbridge; Anna Lewis; Freya Croft; Chris LJ. Frid (Energy Policy, 2025)

Rock mechanical testing of core from the Eos Northern Lights CCS confirmation well and implications for the Geomechanics of North Sea CO2 storage - L. Griffiths; N. Thompson; H. Smith; E. Skurtveit; L. Grande (International Journal of Greenhouse Gas Control, 2025)

Amino acid and acylcarnitine profile of Aedes aegypti (L) post-blood feeding, after permethrin exposure, and during the life cycle - Mariana Lizbeth Jiménez-Martínez; Gerardo de Jesús Trujillo-Rodriguez; María de Lourdes Ramírez-Ahuja; Olga Karina Villanueva-Segura; Patricio Adrián Zapata-Morin; Griffith Samuel Lizarraga; Laura E. Martinez-de-Villarreal; Margarita L. Martinez-Fierro; Ivan Delgado-Enciso; Jose Ignacio Gonzalez-Rojas; Adriana E. Flores; Antonio Guzman-Velasco; et al. (Insect Biochemistry and Molecular Biology, 2025)

Alkali-mediated Sr incorporation mechanism and binding capacity of alkali aluminosilicate hydrate in geopolymers - Daniel A. Geddes; Martin C. Stennett; Tom J. Wilkinson; Benjamin E. Griffith; John V. Hanna; John L. Provis; Brant Walkley (Journal of Hazardous Materials, 2025)

A summary and critique of the various spectrophotometric methods used to quantify C-phycocyanin concentration - Eric J. R. Payne; Melinda Griffiths; Susan T. L. Harrison; Marijke A. Fagan-Endres (Journal of Applied Phycology, 2025)
A wide range of research has been conducted on various applications and purification methods of C-phycocyanin (C-PC). In the published literature, there has not been consistency in the methods used to determine the concentration of C-PC within solution. This is an important characteristic to accurately determine the efficiency of a C-PC purification process and the quality of a final C-PC product. This brief report aims to critically evaluate the equations used to calculate C-PC concentration from spectrophotometric readings published in literature by discussing the logic behind the different coefficients and wavelengths used as well as by comparing the concentrations obtained for a Spirulina derived C-PC sample using the various equations. Some of the equations investigated, predominantly those which only differed slightly in the measured wavelengths, generated similar concentration results. However, these were based on work initially done on a specific cyanobacterium, Fremyella diplosiphon (Bennett and Bogorad 1973). Equations generated using other cyanobacteria extracts or even species of macroalgae generated markedly different C-PC concentrations. When these equations have been used in literature, there is often no distinction made as to whether the algal species being investigated is the same as the one used to develop the equation originally. The goal of this investigation was therefore to highlight this issue so that a more consistent and microalgal-species-appropriate approach can be used in the future for quantifying C-PC concentration in solution.

Exploring the activated charcoal adsorption column to improve cosmetic grade C-phycocyanin purification from Spirulina - Eric J. R. Payne; Melinda Griffiths; Susan T. L. Harrison; Marijke A. Fagan-Endres (Journal of Applied Phycology, 2025)
This study investigates the effectiveness of activated charcoal, a common adsorbent, in various packed column configurations in the context of a process to purify C-phycocyanin (C-PC) from Spirulina . The adsorption column performance is considered in isolation and as part of purification trains, which include chitosan treatment and ammonium sulfate precipitation. Operating parameters of interest included activated charcoal particle size, solution retention time in the column and concentration of the Spirulina crude extract used. The feed was a low purity crude extract and the final target was cosmetic grade C-PC (purity > 1.5). A slower column feed flowrate and smaller activated charcoal particle size were shown to improve the degree of C-PC purification via adsorption. Variation of the crude extract concentration did not have a significant effect. In all cases, high C-PC recoveries over the column were achieved. However, use of a single activated charcoal adsorption column was not able to purify the C-PC to cosmetic grade. Cosmetic grade purity (of between 1.68 ± 0.18 and 2.61 ± 0.44) was reached by coupling the column with chitosan treatment and ammonium sulfate precipitation when using a lower feed concentration of 2.60 ± 0.07 mg C-PC mL −1 . A higher concentration feed could not be purified to cosmetic grade within this investigation, confirming that feed concentration affects the efficiency of the activated charcoal column in combination with the other downstream process steps. The overall process had better yields and was able to accommodate a higher concentration of C-PC than reported in literature.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Frameworks and best practices for cumulative impact accounting in offshore energy development - Caitlin D. Kuempel; Jackson Stockbridge; Tess O’Neill; Laura L. Griffiths; Christopher L.J. Frid; Christopher J. Brown (Marine Policy, 2025)

A high-resolution multiproxy speleothem record of Eastern China hydroclimate variation during last glacial maximum - Shuyu Xue; Hongbin Zhang; Michael L. Griffiths; Chengfei He; Yitao Liu; Junhua Huang; Hai Cheng; Wei Guo; Shitou Wu; Jianzong Zhou; Youfeng Ning; Lin Chen; et al. (Quaternary Science Reviews, 2025)

Prenatal exposure to environmental bisphenols over time and their association with childhood asthma, allergic rhinitis and atopic dermatitis in the ECHO consortium - Rachel L. Miller; Yuyan Wang; Jenny Aalborg; Akram N. Alshawabkeh; Deborah H. Bennett; Carrie V. Breton; Jessie P. Buckley; Dana Dabelea; Anne L. Dunlop; Assiamira Ferrara; Griffith Gao; Abigail Gaylord; et al. (Environmental Pollution, 2025)

The Influence of Micro- and Macrocracks on the Permeability of Granite - L. Carbillet; L. Griffiths; M. J. Heap; H. Duwiquet; P. Baud; M. E. S. Violay; T. Reuschlé; L. Guillou-Frottier (Rock Mechanics and Rock Engineering, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Extremely low biodiversity Arctic intertidal habitats as sentinels for environmental change - Huw J. Griffiths; Catherine L. Waller; Stephen J. Roberts; Anna M. Jażdżewska; David S. Hik (Frontiers in Marine Science, 2024)
The Arctic is undergoing dramatic changes, including an unprecedented decline in sea ice. Previous studies have shown the severe structuring impact of sea ice scour upon polar intertidal communities. A dramatic example of the influence of Arctic sea ice is the highly depauperate intertidal of Cambridge Bay (Iqaluktuuttiaq) on Victoria Island, Nunavut, Canada. Cambridge Bay intertidal is dominated by a single species of amphipod crustacean, Gammarus setosus , with rare examples of another amphipod, bivalve molluscs, and oligochaetes. Primary producers are limited to a thin algal film, with no macroalgae present shallower than 2 m water depth. This intertidal biodiversity has remained extremely low since it was first surveyed 70 years ago, however, the seasonal sea ice thickness has been in decline for over 50 years. Given the observed dramatic increases in biodiversity and biomass with decreased sea ice cover elsewhere in the Arctic and the presence of the Canadian High Arctic Research Station, we suggest that the intertidal of Cambridge Bay offers an ideal location for a low cost, low effort, and long-term monitoring of biodiversity change and tipping points that may be influenced by sea ice loss in the Arctic as part of a network intertidal monitoring stations.

The legal and illegal supply chains of sea turtle eggs in Costa Rica - Helen Pheasey; Richard A. Griffiths; David L. Roberts (Environmental Development, 2024)

Decoupled terrestrial temperature and hydroclimate during the Plio-Pleistocene in the East Asian monsoonal region - Shi Qian; Qinmian Xu; Michael L. Griffiths; Huan Yang; Shucheng Xie (Quaternary Science Reviews, 2024)

Predation on Live and Artificial Insect Prey Shows Different Global Latitudinal Patterns - Elena L. Zvereva; Benjamin Adroit; Tommi Andersson; Craig R. A. Barnett; Sofia Branco; Bastien Castagneyrol; Giancarlo Maria Chiarenza; Wesley Dáttilo; Ek del‐Val; Jan Filip; Jory Griffith; Anna L. Hargreaves; et al. (Global Ecology and Biogeography, 2024)
Aim Long‐standing theory predicts that the intensity of biotic interactions increases from high to low latitudes. Studies addressing geographic variation in predation on insect prey have often relied on prey models, which lack many characteristics of live prey. Our goals were to explore global latitudinal patterns of predator attack rates on standardised live insect prey and to compare the patterns in predation on live insects with those on plasticine prey models. Location Global forested areas. Time Period 2021–2023. Major Taxa Arthropods, birds. Methods We measured predation rates in 43 forested locations distributed across five continents from 34.1° S to 69.5° N latitude. At each location, we exposed 20 sets of three bait types, one set per tree. Each set included three live fly larvae (maggots), three live fly puparia and three plasticine models of the puparia. We used glue rings to isolate half of the sets from non‐flying predators. Results Arthropod attack rates on plasticine prey decreased linearly from low to high latitudes, whereas attack rates on maggots had a U shaped distribution, with the lowest predation rates at temperate latitudes and the highest rates at tropical and boreal latitudes. This difference emerged from intensive predator attacks on live maggots, but not on plasticine models, in boreal sites. Site‐specific attack rates of arthropod predators on live and plasticine prey were not correlated. In contrast, bird attack rates on live maggots and plasticine models were positively correlated, but did not show significant latitudinal changes. Main Conclusions Latitudinal patterns in predation differ between major groups of predators and between types of prey. Poleward decreases in both arthropod and combined arthropod and bird predation on plasticine models do not mirror patterns of predation on our live prey, the latter likely reflecting real patterns of predation risk better than do patterns of attack on artificial prey.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Cannabis use in Parkinson’s disease: Patient access to medical cannabis and physician perspective on product safety - Symone T. Griffith; Kendra D. Conrow; Michael Go; Mindy L. McEntee; Raminta Daniulaityte; Majia H. Nadesan; Mathew R. Swinburne; Holly A. Shill; Maxwell C.K. Leung (NeuroToxicology, 2024)

Behavior, site use and demographics of shortfin devil rays, Mobula kuhlii, at a newly-discovered cleaning area in South Africa - M. M. Carpenter; R. J. Y. Perryman; A. D. Marshall; C. L. Griffiths (Marine Biology, 2024)
Many shark and ray species show affinity to specific sites, making these areas critical for their survival. These include cleaning stations: locations on reefs where cleaner fish remove parasites and clean wounds, which is important for maintaining health. Cleaning stations also function as social gathering sites, or resting points, where courtship and mating can occur. In this study, we identify an aggregation site for the shortfin devil ray, Mobula kuhlii (Family Mobulidae) within the Aliwal Shoal Marine Protected Area in KwaZulu-Natal (KZN), South Africa, and document their behavior. Remote underwater video was used to collect footage of M. kuhlii being cleaned by blue streak cleaner wrasse, Labroides dimidiatus . Generalized additive models (GAMs) were used to assess environmental predictors of M. kuhlii presence on Aliwal Shoal. Mixed models were used to assess the same environmental predictors and their correlation with mean M. kuhlii cleaning duration and number of L. dimidiatus bites per second at the identified cleaning station site. M. kuhlii were present in 56% of observation days, with group numbers up to > 150 individuals. Sea surface temperature was a significant predictor for M. kuhlii presence, while a north to south current was significantly associated with longer mean cleaning durations. These results support findings of mobulid studies in KZN that show increased habitat use during summer temperatures (24–25 °C) and suggest these sites to be important for individual health and social interaction. We hope these findings can be used for development of location-specific management plans to safeguard this Endangered species.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Herpes simplex virus type 1 (HSV-1) induced keratitis: nanoparticles and antiviral peptides as a novel topical treatment - I. Ruedas-Torres; Y. Jiménez-Gómez; L. Ortega-Llamas; J. Gómez-Laguna; M. González-Andrades; M. Griffith; L. Cornea Consortium (Journal of Comparative Pathology, 2024)

Performance of fur clips and livestock markers for identifying vaccinated badgers - Clare H. Benton; Amy L. Griffiths; Richard J. Delahay (European Journal of Wildlife Research, 2024)
Marking free-living wild mammals may be desirable during field studies and management interventions; however, doing so presents practical challenges. In the context of disease management interventions, different approaches such as vaccination and culling may be deployed in adjacent areas resulting in a need to identify previously vaccinated individuals to avoid losses of vaccination benefits. Badgers ( Meles meles ) have been identified as a wildlife reservoir of bovine tuberculosis in several countries. In England, the primary means of controlling disease in badger populations has been culling, although policy also includes the use of badger vaccination. Vaccination and culling can therefore increasingly take place in adjacent areas. The current means of marking vaccinated badgers is to apply a fur clip; however, the performance of this method has not been assessed. In this study, we assessed the field performance of livestock markers not previously trialled on badgers. We also assessed the performance of fur clips in terms of (a) how likely they are to be detected on recapture and (b) their detectability using remote cameras. None of the livestock markers trialled persisted well on badger fur. Detectability of fur clips on re-captured badgers fell to 50% in adult badgers by approximately 3 months from application. In cubs, detectability fell to less than 50% within 3 weeks of application. We suggest it is highly likely that, if vaccination and culling were carried out in adjacent areas and fur clipping was the primary means of determining vaccination status, a proportion of recently vaccinated badgers would be removed, particularly cubs. This has important implications for disease control, and we suggest options for minimising such losses.

A data‐driven approach to multiple‐stressor impact assessment for a marine protected area - Laura L. Griffiths; Joel Williams; Christina A. Buelow; Vivitskaia J. Tulloch; Mischa P. Turschwell; Max D. Campbell; David Harasti; Rod M. Connolly; Christopher J. Brown (Conservation Biology, 2024)
The coastal environment is not managed in a way that considers the impact of cumulative threats, despite being subject to threats from all realms (marine, land, and atmosphere). Relationships between threats and species are often nonlinear; thus, current (linear) approaches to estimating the impact of threats may be misleading. We developed a data‐driven approach to assessing cumulative impacts on ecosystems and applied it to explore nonlinear relationships between threats and a temperate reef fish community. We used data on water quality, commercial fishing, climate change, and indicators of recreational fishing and urbanization to build a cumulative threat map of the northern region in New South Wales, Australia. We used statistical models of fish abundance to quantify associations among threats and biophysical covariates and predicted where cumulative impacts are likely to have the greatest impact on fish. We also assessed the performance of no‐take zones (NTZs), to protect fish from cumulative threats across 2 marine protected area networks (marine parks). Fishing had a greater impact on fish than water quality threats (i.e., percent increase above the mean for invertivores was 337% when fishing was removed and was 11% above the mean when water quality was removed inside NTZs), and fishing outside NTZs affected fish abundances inside NTZs. Quantifying the spatial influence of multiple threats enables managers to understand the multitude of management actions required to address threats.

Climate change disrupts the seasonal coupling of plant and soil microbial nutrient cycling in an alpine ecosystem - Arthur A. D. Broadbent; Lindsay K. Newbold; William J. Pritchard; Antonios Michas; Tim Goodall; Irene Cordero; Andrew Giunta; Helen S. K. Snell; Violette V. L. H. Pepper; Helen K. Grant; David X. Soto; Ruediger Kaufmann; et al. (Global Change Biology, 2024)
The seasonal coupling of plant and soil microbial nutrient demands is crucial for efficient ecosystem nutrient cycling and plant production, especially in strongly seasonal alpine ecosystems. Yet, how these seasonal nutrient cycling processes are modified by climate change and what the consequences are for nutrient loss and retention in alpine ecosystems remain unclear. Here, we explored how two pervasive climate change factors, reduced snow cover and shrub expansion, interactively modify the seasonal coupling of plant and soil microbial nitrogen (N) cycling in alpine grasslands, which are warming at double the rate of the global average. We found that the combination of reduced snow cover and shrub expansion disrupted the seasonal coupling of plant and soil N‐cycling, with pronounced effects in spring (shortly after snow melt) and autumn (at the onset of plant senescence). In combination, both climate change factors decreased plant organic N‐uptake by 70% and 82%, soil microbial biomass N by 19% and 38% and increased soil denitrifier abundances by 253% and 136% in spring and autumn, respectively. Shrub expansion also individually modified the seasonality of soil microbial community composition and stoichiometry towards more N‐limited conditions and slower nutrient cycling in spring and autumn. In winter, snow removal markedly reduced the fungal:bacterial biomass ratio, soil N pools and shifted bacterial community composition. Taken together, our findings suggest that interactions between climate change factors can disrupt the temporal coupling of plant and soil microbial N‐cycling processes in alpine grasslands. This could diminish the capacity of these globally widespread alpine ecosystems to retain N and support plant productivity under future climate change.

Enigmatic carbonate isotope values in shark teeth: Evidence for environmental and dietary controls - Molly E. Karnes; Rachel L. Chan; Jonathon P. Kuntz; Michael L. Griffiths; Kenshu Shimada; Martin A. Becker; Harry M. Maisch; Robert A. Eagle; Joan Brenner-Coltrain; Shawn Miller; Sora L. Kim (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

The underwater soundscape of the North Sea - F. Basan; J.-G. Fischer; R. Putland; J. Brinkkemper; C.A.F. de Jong; B. Binnerts; A. Norro; D. Kühnel; L.-A. Ødegaard; M. Andersson; E. Lalander; J. Tougaard; et al. (Marine Pollution Bulletin, 2024)

The Status of South Africa’s Freshwater Fish Fauna: A Spatial Analysis of Diversity, Threat, Invasion, and Protection - Mohammed Kajee; Helen F. Dallas; Charles L. Griffiths; Cornelius J. Kleynhans; Jeremy M. Shelton (Fishes, 2023)
In South Africa, freshwater habitats are among the most threatened ecosystems, and freshwater fishes are the most threatened species group. Understanding patterns in freshwater fish diversity, threat, invasion, and protection status are vital for their management. However, few studies have undertaken such analyses at ecologically and politically appropriate spatial scales, largely because of limited access to comprehensive biodiversity data sets. Access to freshwater fish data for South Africa has recently improved through the advent of the Freshwater Biodiversity Information System (FBIS). We used occurrence records downloaded from the FBIS to evaluate spatial patterns in distribution, diversity, threat, invasion, and protection status of freshwater fishes in South Africa. Results show that record density varies spatially, at both primary catchment and provincial scales. The diversity of freshwater fishes also varied spatially: native species hotspots were identified at a provincial level in the Limpopo, Mpumalanga, and KwaZulu-Natal provinces; endemic species hotspots were identified in the Western Cape; and threatened species hotspots in the Western Cape, Mpumalanga, Eastern Cape, and KwaZulu-Natal. Non-native species distributions mirrored threatened species hotspots in the Western Cape, Mpumalanga, Eastern Cape, and KwaZulu-Natal. Some 47% of threatened species records fell outside of protected areas, and 38% of non-native species records fell within protected areas. Concerningly, 58% of the distribution ranges of threatened species were invaded by non-native species.

Northern high-latitude sea ice variation linked with East Asian monsoon anomalies during the Younger Dryas - Xiaolong Chen; Hongbin Zhang; Michael L. Griffiths; Xiaogui Peng; Liangzhe Yang; Ming Yu; Junhua Huang; Shuyu Xue; Hai Cheng; Shuai Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

A holistic and comprehensive data approach validates the distribution of the critically endangered flapper skate ( Dipturus intermedius ) - Amy Garbett; Sophie L. Loca; Thomas Barreau; Manuel Biscoito; Caroline Bradley; Joe Breen; Maurice Clarke; Jim R. Ellis; Andrew M. Griffiths; Gary Hannon; Klara Jakobsdóttir; Claudia Junge; et al. (Journal of Fish Biology, 2023)
Morphological similarities between skates of the genus Dipturus in the north‐eastern Atlantic and Mediterranean have resulted in longstanding confusion, misidentification and misreporting. Current evidence indicates that the common skate is best explained as two species, the flapper skate ( Dipturus intermedius ) and the common blue skate ( D. batis ). However, some management and conservation initiatives developed prior to the separation continue to refer to common skate (as ‘ D. batis’ ). This taxonomic uncertainty can lead to errors in estimating population viability, distribution range, and impact on fisheries management and conservation status. Here, we demonstrate how a concerted taxonomic approach, using molecular data and a combination of survey, angler and fisheries data, in addition to expert witness statements, can be used to build a higher resolution picture of the current distribution of D. intermedius . Collated data indicate that flapper skate has a more constrained distribution compared to the perceived distribution of the ‘common skate’, with most observations recorded from Norway and the western and northern seaboards of Ireland and Scotland, with occasional specimens from Portugal and the Azores. Overall, the revised spatial distribution of D. intermedius has significantly reduced the extant range of the species, indicating a possibly fragmented distribution range.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Barium isotope fractionation in barite–fluid systems at chemical equilibrium - J.T. Middleton; W.-L. Hong; A. Paytan; M.E. Auro; E.M. Griffith; T.J. Horner (Chemical Geology, 2023)

Multi-decade catches of manta rays (Mobula alfredi, M. birostris) from South Africa reveal significant decline - Michelle Carpenter; Denham Parker; Matthew L. Dicken; Charles L. Griffiths (Frontiers in Marine Science, 2023)
Manta rays ( Mobula alfredi and M. birostris ) are poorly understood in South Africa, despite their ecological importance and charismatic appeal. This study analyzed a 41-year dataset from the KwaZulu-Natal bather protection program to investigate catch per unit effort between 1981-2021. We used Generalized Additive Models and the probability of encounter to assess annual and seasonal trends, as well as the effect of location and moon phases on catch rates. We also evaluated the size composition and demographics of caught manta rays using the same dataset. Our analysis revealed a significant decline in overall manta ray catches since the late 1990s (p<0.0001), with increased catch rates during summer, suggesting seasonal visitation to South African waters. We found that manta rays were caught at least once in all 46 netted beaches along the 350 km span of coastline, but with significantly more catches in the Central Area, between Anstey’s beach in the north and Mtwalume in the south. We also observed that moon phase had an effect on manta ray presence, with significantly more catches during spring tides at new and full moon phases. Over half of the caught individuals were juveniles, and a total of 841 individuals (52% of the total catch) belonged to the confirmed juvenile size class (1400-2500 mm disc width). We further found that a greater proportion (70%) of juveniles were caught in the southernmost sampled area, from Hibberdene in the north to Mzamba in the south. These findings highlight the importance of South African waters as a seasonal habitat for manta rays along the southern African coastline. The significant decline and spatial-temporal patterns we observed have critical implications for management and conservation efforts. Our study provides valuable baseline data for future research and underscores the need for continued monitoring and protection of these iconic marine species.

Unusual composition and vertical zonation patterns amongst the biota of pebble and cobble shores - Amanda Robbins; Charles L. Griffiths (Estuarine, Coastal and Shelf Science, 2023)

Differential Strigeid Infection Patterns in Male Morphotypes of Bluegill Sunfish (Lepomis macrochirus) - Erin Atkinson; Brandi Griffith Keller; Nicholas S. Strait; Victoria L. Krist; Michael R. Zimmermann (Acta Parasitologica, 2023)

Longitudinal metatranscriptomic sequencing of Southern California wastewater representing 16 million people from August 2020–21 reveals widespread transcription of antibiotic resistance genes - Jason A. Rothman; Andrew Saghir; Seung-Ah Chung; Nicholas Boyajian; Thao Dinh; Jinwoo Kim; Jordan Oval; Vivek Sharavanan; Courtney York; Amity G. Zimmer-Faust; Kylie Langlois; Joshua A. Steele; et al. (Water Research, 2023)

Finding the sweet spot: drilling precision on shelled molluscs by Octopus vulgaris type III in False Bay, South Africa - Gareth N. Fee; Jennifer Mather; Jannes Landschoff; Charles L. Griffiths (Marine Biology, 2023)

Holocene forcing of East Asian hydroclimate recorded in a subtropical peatland from southeastern China - Xianyu Huang; Hongbin Zhang; Michael L. Griffiths; Bingyan Zhao; Francesco S. R. Pausata; Clay Tabor; Junwu Shu; Shucheng Xie (Climate Dynamics, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Associations between DNA methylation and telomere length during early life: Insight from wild zebra finches ( Taeniopygia guttata ) - Elizabeth L. Sheldon; Riccardo Ton; Winnie Boner; Pat Monaghan; Shirley Raveh; Aaron W. Schrey; Simon C. Griffith (Molecular Ecology, 2022)
Telomere length and DNA methylation (DNAm) are two promising biomarkers of biological age. Environmental factors and life history traits are known to affect variation in both these biomarkers, especially during early life, yet surprisingly little is known about their reciprocal association, especially in natural populations. Here, we explore how variation in DNAm, growth rate, and early‐life conditions are associated with telomere length changes during development. We tested these associations by collecting data from wild, nestling zebra finches in the Australian desert. We found that increases in the level of DNAm were negatively correlated with telomere length changes across early life. We also confirm previously documented effects of post hatch growth rate and clutch size on telomere length in a natural ecological context for a species that has been extensively studied in the laboratory. However, we did not detect any effect of ambient temperature during developmental on telomere length dynamics. We also found that the absolute telomere length of wild zebra finches, measured using the in‐gel TRF method, was similar to that of captive birds. Our findings highlight exciting new opportunities to link and disentangle potential relationships between DNA based biomarkers of ageing, and of physiological reactions to environmental change.

Comparisons of macrofaunal communities occupying shores across the full particle-size spectrum reveals pebble beaches to be a distinct coastal habitat type - A Robbins; CL Griffiths; L Nefdt (African Journal of Marine Science, 2022)

Investigation of Mitochondrial Related Variants in a Cerebral Small Vessel Disease Cohort - P. J. Dunn; N. R. Harvey; N. Maksemous; R. A. Smith; H. G. Sutherland; L. M. Haupt; L. R. Griffiths (Molecular Neurobiology, 2022)
Monogenic forms of cerebral small vessel disease (CSVD) can be caused by both variants in nuclear DNA and mitochondrial DNA (mtDNA). Mitochondrial encephalopathy, lactic acidosis, and stroke-like episodes (MELAS) is known to have a phenotype similar to Cerebral Autosomal Dominant Arteriopathy with Sub-cortical Infarcts and Leukoencephalopathy (CADASIL), and can be caused by variants in the mitochondrial genome and in several nuclear-encoded mitochondrial protein (NEMP) genes. The aim of this study was to screen for variants in the mitochondrial genome and NEMP genes in a NOTCH3 -negative CADASIL cohort, to identify a potential link between mitochondrial dysfunction and CSVD pathology. Whole exome sequencing was performed for 50 patients with CADASIL-like symptomology on the Ion Torrent system. Mitochondrial sequencing was performed using an in-house designed protocol with sequencing run on the Ion GeneStudio S5 Plus (S5 +). NEMP genes and mitochondrial sequencing data were examined for rare (MAF < 0.001), non-synonymous variants that were predicted to have a deleterious effect on the protein. We identified 29 candidate NEMP variants that had links to either MELAS-, encephalopathy-, or Alzheimer’s disease–related phenotypes. Based on these changes, variants affecting POLG , MTO1 , LONP1 , NDUFAF6 , NDUFB3 , and TCIRG1 were thought to play a potential role in CSVD pathology in this cohort. Overall, the exploration of the mitochondrial genome identified a potential role for mitochondrial related proteins and mtDNA variants contributing to CSVD pathologies.

Long-Term Drought and Warming Alter Soil Bacterial and Fungal Communities in an Upland Heathland - Fiona M. Seaton; Sabine Reinsch; Tim Goodall; Nicola White; Davey L. Jones; Robert I. Griffiths; Simon Creer; Andy Smith; Bridget A. Emmett; David A. Robinson (Ecosystems, 2022)
The response of soil microbial communities to a changing climate will impact global biogeochemical cycles, potentially leading to positive and negative feedbacks. However, our understanding of how soil microbial communities respond to climate change and the implications of these changes for future soil function is limited. Here, we assess the response of soil bacterial and fungal communities to long-term experimental climate change in a heathland organo-mineral soil. We analysed microbial communities using Illumina sequencing of the 16S rRNA gene and ITS2 region at two depths, from plots undergoing 4 and 18 years of in situ summer drought or warming. We also assessed the colonisation of Calluna vulgaris roots by ericoid and dark septate endophytic (DSE) fungi using microscopy after 16 years of climate treatment. We found significant changes in both the bacterial and fungal communities in response to drought and warming, likely mediated by changes in soil pH and electrical conductivity. Changes in the microbial communities were more pronounced after a longer period of climate manipulation. Additionally, the subsoil communities of the long-term warmed plots became similar to the topsoil. Ericoid mycorrhizal colonisation decreased with depth while DSEs increased; however, these trends with depth were removed by warming. We largely ascribe the observed changes in microbial communities to shifts in plant cover and subsequent feedback on soil physicochemical properties, especially pH. Our results demonstrate the importance of considering changes in soil microbial responses to climate change across different soil depths and after extended periods of time.

Additions to the marine decapod (Crustacea: Decapoda) fauna of South Africa - Jannes Landschoff; Charles L. Griffiths; Lara J. Atkinson; Kerry J. Sink; Thomas P. Botha (Western Indian Ocean Journal of Marine Science, 2022)
This report adds five previously unreported species to the decapod crustacean fauna of South Africa, as well as removing one species previously listed in error. It also documents locality (and/or reference specimen) data for 12 other species, most of which had been depicted in regional field guides, but without reporting when and where they had been collected. Almost all the species added were already known from adjacent African countries and their ranges are here extended into South Africa. Although some of these records are based on photographs, rather than collected specimens, it is argued that such records should be accepted as adequate evidence for inclusion of at least visually-distinctive crustacean species into the regional fauna.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Spatio-Temporal Distribution of Juvenile Oceanic Whitetip Shark Incidental Catch in the Western Indian Ocean - Leire Lopetegui-Eguren; Jan Jaap Poos; Haritz Arrizabalaga; Gency L. Guirhem; Hilario Murua; Nerea Lezama-Ochoa; Shane P. Griffiths; Jon Ruiz Gondra; Philippe S. Sabarros; José Carlos Báez; Maria José Juan-Jordá (Frontiers in Marine Science, 2022)
Oceanic whitetip shark ( Carcharhinus longimanus ) is an important top predator in pelagic ecosystems currently classified as globally Critically Endangered by the International Union for the Conservation of Nature. This species is incidentally caught by fisheries targeting highly migratory tunas and billfishes throughout the Indian Ocean. Understanding the temporal, spatial and environmental factors influencing the capture of this species is essential to reduce incidental catches. In this study, we used generalized additive models to analyze the spatio-temporal distributions of the juvenile oceanic whitetip shark catches and the environmental conditions in the western Indian Ocean using observer data from 2010 to 2020 of the European Union and associated flags purse seine fishery. We found sea surface temperature and nitrate concentration to be the most important environmental variables predicting the probability of catching an oceanic whitetip shark. A higher probability of capture was predicted in areas where sea surface temperature was below 24°C and with low nitrate concentrations close to zero and intermediate values (1.5-2.5 mmol.m -3 ). We also found a higher probability of capture in sets on fish aggregating devices than in sets on free schools of tuna. The Kenya and Somalia basin was identified to have higher probabilities of capture during the summer monsoon (June to September) when upwelling of deep cold waters occurs. We provide the first prediction maps of capture probabilities and insights into the environmental preferences of oceanic whitetip shark in the western Indian Ocean. However, the causal mechanisms behind these insights should be explored in future studies before they can be used to design spatial management and conservation strategies, such as time-area closures, for bycatch avoidance.

Acoustic‐based estimates of Cuvier's beaked whale ( Ziphius cavirostris ) density and abundance along the U.S. West Coast from drifting hydrophone recorders - Jay Barlow; Jeffrey E. Moore; Jennifer L. K. McCullough; Emily T. Griffiths (Marine Mammal Science, 2022)
An acoustic survey of Cuvier's beaked whales ( Ziphius cavirostris ) was conducted off the U.S. West Coast in August and September 2016 using drifting recorder systems with a vertical array of two hydrophones at a depth of ~110 m. Recorders were deployed 22 times to representatively cover a 1,058,000 km 2 study area from the shelf break to ~556 km offshore. Vertical angles to echolocation pulses were measured using the signal time‐difference‐of‐arrival on the two hydrophones. Echolocation pulses of Cuvier's beaked whales were identified from their arrival angles (always from below the array) and unique acoustic characteristics. The density and abundance of Cuvier's beaked whales were estimated using a group‐based point‐transect analysis with 2 min time snapshots. The area effectively surveyed was estimated using a maximum simulated likelihood approach to fit the observed distribution of signal arrival angles. The acoustic availability of whales during their dive cycle was estimated from the duration of acoustic encounters using a mark‐recapture approach. Overall, Cuvier's beaked whales were present during 0.60% of snapshots, and their estimated average density is 5.12 animals per 1,000 km 2 ( CV = 0.27). Their estimated abundance in the study area is 5,454 individuals (95% credibility intervals: 3,151 to 8,907).

Representing plant diversity in land models: An evolutionary approach to make “Functional Types” more functional - Leander D. L. Anderegg; Daniel M. Griffith; Jeannine Cavender‐Bares; William J. Riley; Joseph A. Berry; Todd E. Dawson; Christopher J. Still (Global Change Biology, 2022)
Plants are critical mediators of terrestrial mass and energy fluxes, and their structural and functional traits have profound impacts on local and global climate, biogeochemistry, biodiversity, and hydrology. Yet, Earth System Models (ESMs), our most powerful tools for predicting the effects of humans on the coupled biosphere–atmosphere system, simplify the incredible diversity of land plants into a handful of coarse categories of “Plant Functional Types” (PFTs) that often fail to capture ecological dynamics such as biome distributions. The inclusion of more realistic functional diversity is a recognized goal for ESMs, yet there is currently no consistent, widely accepted way to add diversity to models, that is, to determine what new PFTs to add and with what data to constrain their parameters. We review approaches to representing plant diversity in ESMs and draw on recent ecological and evolutionary findings to present an evolution‐based functional type approach for further disaggregating functional diversity. Specifically, the prevalence of niche conservatism, or the tendency of closely related taxa to retain similar ecological and functional attributes through evolutionary time, reveals that evolutionary relatedness is a powerful framework for summarizing functional similarities and differences among plant types. We advocate that Plant Functional Types based on dominant evolutionary lineages (“Lineage Functional Types”) will provide an ecologically defensible, tractable, and scalable framework for representing plant diversity in next‐generation ESMs, with the potential to improve parameterization, process representation, and model benchmarking. We highlight how the importance of evolutionary history for plant function can unify the work of disparate fields to improve predictive modeling of the Earth system.

Maternal Nanomaterial Inhalation Exposure: Critical Gestational Period in the Uterine Microcirculation is Angiotensin II Dependent - Krista L. Garner; Elizabeth C. Bowdridge; Julie A. Griffith; Evan DeVallance; Madison G. Seman; Kevin J. Engels; Caroline P. Groth; William T. Goldsmith; Kim Wix; Thomas P. Batchelor; Timothy R. Nurkiewicz (Cardiovascular Toxicology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

An exploratory study to investigate the association between age, physical activity, femoral trochlear cartilage thickness and biomarkers of tissue metabolism in adult males - Harry M. Roberts; Claire L. Griffith-McGeever; Julian A. Owen; Lewis Angell; Jonathan P. Moore; Jeanette M. Thom (European Journal of Applied Physiology, 2021)
Purpose To investigate the association between age, physical activity, femoral trochlear cartilage thickness and biomarkers of tissue metabolism in a cross-sectional sample of adult males. This study utilizes several emerging biomarkers that have been associated with early joint degenerative changes; serum COMP (cartilage oligomeric matrix protein), HA (hyaluronan) and lubricin. Methods Eighty-one males (age: mean (range): 43(18–70) years; body mass index: 25.2 (21.0–30.6) kg/m 2 ) volunteered. Resting serum COMP, HA and lubricin concentrations were determined via commercially available enzyme-linked immunosorbent assay (ELISA) and femoral trochlear cartilage thickness via supra-patellar ultrasound imaging. Physical activity levels were assessed using questionnaires. Statistical analyses were performed using correlation and regression analyses. Results Age was correlated with lateral trochlear cartilage thickness ( r = − 0.372; p < 0.01) and serum COMP ( r = 0.342; p < 0.01). 7-day physical activity was correlated with serum COMP ( r = 0.357, p < 0.01), and 12-month physical activity with both lateral trochlear cartilage thickness ( r = 0.340, p = 0.01) and serum HA ( r = 0.296, p < 0.05). Regression analyses revealed that age significantly accounted for the variability in lateral cartilage thickness and serum COMP, following the adjustment for potential cofounders. However, the association between age and lateral trochlear cartilage thickness was not moderated by physical activity levels (all p > 0.05). Conclusion This study indicates that older age may be associated with thinner lateral trochlear cartilage and higher cartilage turnover. Being physically active may also be positive for lateral trochlear cartilage thickness. However, overall, both age and physical activity level only account for a small amount of the variability in cartilage thickness and serum biomarkers.

Responses of Southern Ocean Seafloor Habitats and Communities to Global and Local Drivers of Change - Madeleine J. Brasier; David Barnes; Narissa Bax; Angelika Brandt; Anne B. Christianson; Andrew J. Constable; Rachel Downey; Blanca Figuerola; Huw Griffiths; Julian Gutt; Susanne Lockhart; Simon A. Morley; et al. (Frontiers in Marine Science, 2021)
Knowledge of life on the Southern Ocean seafloor has substantially grown since the beginning of this century with increasing ship-based surveys and regular monitoring sites, new technologies and greatly enhanced data sharing. However, seafloor habitats and their communities exhibit high spatial variability and heterogeneity that challenges the way in which we assess the state of the Southern Ocean benthos on larger scales. The Antarctic shelf is rich in diversity compared with deeper water areas, important for storing carbon (“blue carbon”) and provides habitat for commercial fish species. In this paper, we focus on the seafloor habitats of the Antarctic shelf, which are vulnerable to drivers of change including increasing ocean temperatures, iceberg scour, sea ice melt, ocean acidification, fishing pressures, pollution and non-indigenous species. Some of the most vulnerable areas include the West Antarctic Peninsula, which is experiencing rapid regional warming and increased iceberg-scouring, subantarctic islands and tourist destinations where human activities and environmental conditions increase the potential for the establishment of non-indigenous species and active fishing areas around South Georgia, Heard and MacDonald Islands. Vulnerable species include those in areas of regional warming with low thermal tolerance, calcifying species susceptible to increasing ocean acidity as well as slow-growing habitat-forming species that can be damaged by fishing gears e.g., sponges, bryozoan, and coral species. Management regimes can protect seafloor habitats and key species from fishing activities; some areas will need more protection than others, accounting for specific traits that make species vulnerable, slow growing and long-lived species, restricted locations with optimum physiological conditions and available food, and restricted distributions of rare species. Ecosystem-based management practices and long-term, highly protected areas may be the most effective tools in the preservation of vulnerable seafloor habitats. Here, we focus on outlining seafloor responses to drivers of change observed to date and projections for the future. We discuss the need for action to preserve seafloor habitats under climate change, fishing pressures and other anthropogenic impacts.

Negative impacts of invasive predators used as biological control agents against the pest snail Lissachatina fulica: the snail Euglandina ‘rosea’ and the flatworm Platydemus manokwari - Justin Gerlach; Gary M. Barker; Cindy S. Bick; Philippe Bouchet; Gilianne Brodie; Carl C. Christensen; Timothy Collins; Trevor Coote; Robert H. Cowie; G. Curt Fiedler; Owen L. Griffiths; F. B. Vincent Florens; et al. (Biological Invasions, 2021)
Since 1955 snails of the Euglandina rosea species complex and Platydemus manokwari flatworms were widely introduced in attempted biological control of giant African snails ( Lissachatina fulica ) but have been implicated in the mass extinction of Pacific island snails. We review the histories of the 60 introductions and their impacts on L. fulica and native snails. Since 1993 there have been unofficial releases of Euglandina within island groups. Only three official P. manokwari releases took place, but new populations are being recorded at an increasing rate, probably because of accidental introduction. Claims that these predators controlled L. fulica cannot be substantiated; in some cases pest snail declines coincided with predator arrival but concomitant declines occurred elsewhere in the absence of the predator and the declines in some cases were only temporary. In the Hawaiian Islands, although there had been some earlier declines of native snails, the Euglandina impacts on native snails are clear with rapid decline of many endemic Hawaiian Achatinellinae following predator arrival. In the Society Islands, Partulidae tree snail populations remained stable until Euglandina introduction, when declines were extremely rapid with an exact correspondence between predator arrival and tree snail decline. Platydemus manokwari invasion coincides with native snail declines on some islands, notably the Ogasawara Islands of Japan, and its invasion of Florida has led to mass mortality of Liguus spp. tree snails. We conclude that Euglandina and P. manokwari are not effective biocontrol agents, but do have major negative effects on native snail faunas. These predatory snails and flatworms are generalist predators and as such are not suitable for biological control.

Carbon flux and forest dynamics: Increased deadwood decomposition in tropical rainforest tree‐fall canopy gaps - Hannah M. Griffiths; Paul Eggleton; Nicole Hemming‐Schroeder; Tom Swinfield; Joel S. Woon; Steven D. Allison; David A. Coomes; Louise A. Ashton; Catherine L. Parr (Global Change Biology, 2021)
Tree mortality rates are increasing within tropical rainforests as a result of global environmental change. When trees die, gaps are created in forest canopies and carbon is transferred from the living to deadwood pools. However, little is known about the effect of tree‐fall canopy gaps on the activity of decomposer communities and the rate of deadwood decay in forests. This means that the accuracy of regional and global carbon budgets is uncertain, especially given ongoing changes to the structure of rainforest ecosystems. Therefore, to determine the effect of canopy openings on wood decay rates and regional carbon flux, we carried out the first assessment of deadwood mass loss within canopy gaps in old‐growth rainforest. We used replicated canopy gaps paired with closed canopy sites in combination with macroinvertebrate accessible and inaccessible woodblocks to experimentally partition the relative contribution of microbes vs. termites to decomposition within contrasting understorey conditions. We show that over a 12 month period, wood mass loss increased by 63% in canopy gaps compared with closed canopy sites and that this increase was driven by termites. Using LiDAR data to quantify the proportion of canopy openings in the study region, we modelled the effect of observed changes in decomposition within gaps on regional carbon flux. Overall, we estimate that this accelerated decomposition increases regional wood decay rate by up to 18.2%, corresponding to a flux increase of 0.27 Mg C ha −1 year −1 that is not currently accounted for in regional carbon budgets. These results provide the first insights into how small‐scale disturbances in rainforests can generate hotspots for decomposer activity and carbon fluxes. In doing so, we show that including canopy gap dynamics and their impacts on wood decomposition in forest ecosystems can help improve the predictive accuracy of the carbon cycle in land surface models.

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Breaking All the Rules: The First Recorded Hard Substrate Sessile Benthic Community Far Beneath an Antarctic Ice Shelf - Huw J. Griffiths; Paul Anker; Katrin Linse; Jamie Maxwell; Alexandra L. Post; Craig Stevens; Slawek Tulaczyk; James A. Smith (Frontiers in Marine Science, 2021)
The seafloor beneath floating ice shelves accounts roughly a third of the Antarctic’s 5 million km 2 of continental shelf. Prior to this study, our knowledge of these habitats and the life they support was restricted to what has been observed from eight boreholes drilled for geological and glaciological studies. The established theory of sub-ice shelf biogeography is that both functional and taxonomic diversities decrease along a nutrient gradient with distance from the ice shelf front, resulting in a depauperate fauna, dominated by mobile scavengers and predators toward the grounding line. Mobile macro-benthic life and mega-benthic life have been observed as far as 700 km under an ice shelf. New observations from two boreholes in the Filchner-Ronne Ice Shelf challenge the idea that sessile organisms reduce in prevalence the further under the ice you go. The discovery of an established community consisting of only sessile, probably filter feeding, organisms (sponges and other taxa) on a boulder 260 km from the ice front raises significant questions, especially when the local currents suggest that this community is somewhere between 625 km and 1500 km in the direction of water flow from the nearest region of photosynthesis. This new evidence requires us to rethink our ideas with regard to the diversity of community types found under ice shelves, the key factors which control their distribution and their vulnerability to environmental change and ice shelf collapse.

Communal roosting shows dynamics predicted by direct and indirect nepotism in chestnut-crowned babblers - Fumiaki Y. Nomano; James L. Savage; Lee A. Rollins; Simon C. Griffith; Andrew F. Russell (Behavioral Ecology and Sociobiology, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Chondrichthyans from the Lower Clayton Limestone Unit of the Midway Group (Paleocene) near Malvern, Arkansas, USA, with comments on the K/Pg boundary - Harry M. Maisch; Martin A. Becker; Michael L. Griffiths (PalZ, 2020)

Soil nutrients and precipitation are major drivers of global patterns of grass leaf silicification - Kathleen M. Quigley; Daniel M. Griffith; George L. Donati; T. Michael Anderson (Ecology, 2020)
Grasses accumulate high concentrations of silicon (Si) in their tissues, with potential benefits including herbivore defense, improved water balance, and reduced leaf construction costs. Although Si is one of the most widely varying leaf constituents among individuals, species, and ecosystems, the environmental forces driving this variation remain elusive and understudied. To understand relationships between environmental factors and grass Si accumulation better, we analyzed foliar chemistry of grasses from 17 globally distributed sites where nutrient inputs and grazing were manipulated. These sites span natural gradients in temperature, precipitation, and underlying soil properties, which allowed us to assess the relative importance of soil moisture and nutrients across variation in climate. Foliar Si concentration did not respond to large mammalian grazer exclusion, but significant variation in herbivore abundance among sites may have precluded the observation of defoliation effects at these sites. However, nutrient addition consistently reduced leaf Si, especially at sites with low soil nitrogen prior to nutrient addition. Additionally, a leaf‐level trade‐off between Si and carbon (C) existed that was stronger at arid sites than mesic sites. Our results suggest soil nutrient limitation favors investment in Si over C‐based leaf construction, and that fixing C is especially costly relative to assimilating Si when water is limiting. Our results demonstrate the importance of soil nutrients and precipitation as key drivers of global grass silicification patterns.

Tiered analysis of whole-exome sequencing for epilepsy diagnosis - Paul J. Dunn; Bridget H. Maher; Cassie L. Albury; Shani Stuart; Heidi G. Sutherland; Neven Maksemous; Miles C. Benton; Robert A. Smith; Larisa M. Haupt; Lyn R. Griffiths (Molecular Genetics and Genomics, 2020)

Genetic variants associated with exercise performance in both moderately trained and highly trained individuals - N. R. Harvey; S. Voisin; P. J. Dunn; H. Sutherland; X. Yan; M. Jacques; I. D. Papadimitriou; L. J. Haseler; K. J. Ashton; L. M. Haupt; N. Eynon; L. R. Griffiths (Molecular Genetics and Genomics, 2020)

Geographic variation in life-history traits of the long-lived monacanthid Meuschenia scaber (Monacanthidae) - V. Visconti; E. D. L. Trip; M. H. Griffiths; Kendall D. Clements (Marine Biology, 2020)

Coralline red algae—a new host taxon for burrowing barnacles (Cirripedia, Acrothoracica) - Thomas P. A. Botha; Charles L. Griffiths; Gavin W. Maneveldt (Marine Biodiversity, 2020)

Triassic to Neogene tectono-magmatic events within Lorne Basin evolution, coastal New South Wales, eastern Australia - F. L. Sutherland; I. T. Graham; H. Zwingmann; D. J. Och; C. J. Gardner; R. E. Pogson; R. J. Griffiths; A. Lay (Australian Journal of Earth Sciences, 2020)

Reproductive coordination breeds success: the importance of the partnership in avian sperm biology - Laura L. Hurley; Melissah Rowe; Simon C. Griffith (Behavioral Ecology and Sociobiology, 2020)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Description of a new beaked whale echolocation pulse type in the California Current - Emily T. Griffiths; Jennifer L. Keating; Jay Barlow; Jeffrey E. Moore (Marine Mammal Science, 2019)

Northern areas as refugia for temperate species under current climate warming: Atlantic salmon ( Salmo salar L.) as a model in northern Europe - Jose L. Horreo; Andrew M. Griffiths; Gonzalo Machado‐Schiaffino; Jamie R. Stevens; Eva Garcia‐Vazquez (Journal of Fish Biology, 2019)
In this work, patterns of geographical genetic diversity in Atlantic salmon Salmo salar were studied across the whole Atlantic Arc; whether these patterns (and thus genetic population structure) were affected by water temperatures was also evaluated. Salmo salar populations were characterized using microsatellite loci and then analysed with reference to ocean surface temperature data from across the region. Analysis showed the presence of a latitudinal cline of genetic variability (higher in northern areas) and water temperatures (sea surface temperatures) determining genetic population structure (the latter in combination with genetic drift in southern populations). Under the current global change scenario, northern areas of Europe would constitute refugia for diversity in the future. This is effectively the inverse of what appears to have happened in glacial refugia during the last glacial maximum. From this perspective, the still abundant and large northern populations S. salar should be considered as precious as the small almost relict southern ones and given appropriate protection. Careful management of the species, coordinated across countries and latitudes, is needed in order to avoid its extinction in Europe.

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Isotopic evidence of biotrophy and unusual nitrogen nutrition in soil‐dwelling Hygrophoraceae - Hans Halbwachs; Gary L. Easton; Roland Bol; Erik A. Hobbie; Mark H Garnett; Derek Peršoh; Liz Dixon; Nick Ostle; Peter Karasch; Gareth W. Griffith (Environmental Microbiology, 2018)
Summary Several lines of evidence suggest that the agaricoid, non‐ectomycorrhizal members of the family Hygrophoraceae (waxcaps) are biotrophic with unusual nitrogen nutrition. However, methods for the axenic culture and lab‐based study of these organisms remain to be developed, so our current knowledge is limited to field‐based investigations. Addition of nitrogen, lime or organophosphate pesticide at an experimental field site (Sourhope) suppressed fruiting of waxcap basidiocarps. Furthermore, stable isotope natural abundance in basidiocarps were unusually high in 15 N and low in 13 C, the latter consistent with mycorrhizal nutritional status. Similar patterns were found in waxcap basidiocarps from diverse habitats across four continents. Additional data from 14 C analysis of basidiocarps and 13 C pulse label experiments suggest that these fungi are not saprotrophs but rather biotrophic endophytes and possibly mycorrhizal. The consistently high but variable δ 15 N values (10–20‰) of basidiocarps further indicate that N acquisition or processing differ from other fungi; we suggest that N may be derived from acquisition of N via soil fauna high in the food chain.

Genetic diversity through time and space: diversity and demographic history from natural history specimens and serially sampled contemporary populations of the threatened Gouldian finch (Erythrura gouldiae) - Peri E. Bolton; Lee A. Rollins; James Brazill-Boast; Kimberley L. Maute; Sarah Legge; Jeremy J. Austin; Simon C. Griffith (Conservation Genetics, 2018)

Herbivory and eutrophication mediate grassland plant nutrient responses across a global climatic gradient - T. Michael Anderson; Daniel M. Griffith; James B. Grace; Eric M. Lind; Peter B. Adler; Lori A. Biederman; Dana M. Blumenthal; Pedro Daleo; Jennifer Firn; Nicole Hagenah; W. Stanley Harpole; Andrew S. MacDougall; et al. (Ecology, 2018)
Plant stoichiometry, the relative concentration of elements, is a key regulator of ecosystem functioning and is also being altered by human activities. In this paper we sought to understand the global drivers of plant stoichiometry and compare the relative contribution of climatic vs. anthropogenic effects. We addressed this goal by measuring plant elemental (C, N, P and K) responses to eutrophication and vertebrate herbivore exclusion at eighteen sites on six continents. Across sites, climate and atmospheric N deposition emerged as strong predictors of plot‐level tissue nutrients, mediated by biomass and plant chemistry. Within sites, fertilization increased total plant nutrient pools, but results were contingent on soil fertility and the proportion of grass biomass relative to other functional types. Total plant nutrient pools diverged strongly in response to herbivore exclusion when fertilized; responses were largest in ungrazed plots at low rainfall, whereas herbivore grazing dampened the plant community nutrient responses to fertilization. Our study highlights (1) the importance of climate in determining plant nutrient concentrations mediated through effects on plant biomass, (2) that eutrophication affects grassland nutrient pools via both soil and atmospheric pathways and (3) that interactions among soils, herbivores and eutrophication drive plant nutrient responses at small scales, especially at water‐limited sites.

Predictive ability of genomic selection models in a multi-population perennial ryegrass training set using genotyping-by-sequencing - Marty J. Faville; Siva Ganesh; Mingshu Cao; M. Z. Zulfi Jahufer; Timothy P. Bilton; H. Sydney Easton; Douglas L. Ryan; Jason A. K. Trethewey; M. Philip Rolston; Andrew G. Griffiths; Roger Moraga; Casey Flay; et al. (Theoretical and Applied Genetics, 2018)

Reproductive biology of the leatherjacket, Meuschenia scaber (Monacanthidae) (Forster 1801) in the Hauraki Gulf, New Zealand - Valerio Visconti; Elizabeth D. L. Trip; Marc H. Griffiths; Kendall D. Clements (New Zealand Journal of Marine and Freshwater Research, 2018)
The leatherjacket Meuschenia scaber is widely distributed in Australasian waters, and is a valued bycatch of inshore bottom trawl fisheries although little is known of its life history. Here, we describe the reproductive biology of the species based on 651 leatherjackets sampled in the Hauraki Gulf, New Zealand, between July 2014 and March 2016. The maximum total length ( L T ) recorded for females and males were 320 and 315 mm, respectively, with both sexes present in all size classes. Monthly analysis of gonad condition revealed a clear spawning season from late austral winter to early summer (August–December), and histological analysis of the ovaries revealed that M. scaber is an indeterminate serial spawning gonochorist. The estimated sizes at sexual maturity ( L 50 ) for females (189.9 mm L T ) and males (188.4 mm L T ) did not differ significantly. Relatively small testes, sexual dimorphism and underwater observation of nesting suggest that M. scaber is a paired spawner.

Understanding and managing fish populations: keeping the toolbox fit for purpose - J. R. Paris; K. D. Sherman; E. Bell; C. Boulenger; C. Delord; M. B. M. El‐Mahdi; E. A. Fairfield; A. M. Griffiths; C. Gutmann Roberts; R. D. Hedger; L. E. Holman; L. H. Hooper; et al. (Journal of Fish Biology, 2018)
Wild fish populations are currently experiencing unprecedented pressures, which are projected to intensify in the coming decades. Developing a thorough understanding of the influences of both biotic and abiotic factors on fish populations is a salient issue in contemporary fish conservation and management. During the 50th Anniversary Symposium of The Fisheries Society of the British Isles at the University of Exeter, UK, in July 2017, scientists from diverse research backgrounds gathered to discuss key topics under the broad umbrella of ‘Understanding Fish Populations’. Below, the output of one such discussion group is detailed, focusing on tools used to investigate natural fish populations. Five main groups of approaches were identified: tagging and telemetry; molecular tools; survey tools; statistical and modelling tools; tissue analyses. The appraisal covered current challenges and potential solutions for each of these topics. In addition, three key themes were identified as applicable across all tool‐based applications. These included data management, public engagement, and fisheries policy and governance. The continued innovation of tools and capacity to integrate interdisciplinary approaches into the future assessment and management of fish populations is highlighted as an important focus for the next 50 years of fisheries research.

Liposomal Irinotecan Accumulates in Metastatic Lesions, Crosses the Blood-Tumor Barrier (BTB), and Prolongs Survival in an Experimental Model of Brain Metastases of Triple Negative Breast Cancer - Afroz S. Mohammad; Jessica I. Griffith; Chris E. Adkins; Neal Shah; Emily Sechrest; Emma L. Dolan; Tori B. Terrell-Hall; Bart S. Hendriks; Helen Lee; Paul R. Lockman (Pharmaceutical Research, 2018)

Life‐history traits of the leatherjacket Meuschenia scaber , a long‐lived monacanthid - V. Visconti; E. D. L. Trip; M. H. Griffiths; K. D. Clements (Journal of Fish Biology, 2018)
The present study describes the age and growth of the leatherjacket Meuschenia scaber , a common Australasian monacanthid and valued by‐catch of the inshore bottom trawl fishery in New Zealand. Age was determined from the sagittal otoliths of 651 individuals collected between July 2014 and March 2016 in the Hauraki Gulf of New Zealand. Otolith sections revealed alternating opaque and translucent zones and edge‐type analysis demonstrated that these are deposited annually. Meuschenia scaber displayed rapid initial growth, with both males and females reaching maturity in 1–2 years and 50% of both sexes matured at 1·5 years. Maximum age differed substantially between the sexes, at 9·8 years for males and 17·1 years for females. Growth rate was similar between sexes, although males reached greater mass at age than females in the early part of the lifespan. The length–mass relationship differed significantly between the sexes, with males displaying negative allometric growth and females isometric growth. Female condition was highest in July, declined in August with the onset of spawning and showed a slight peak in January and February, immediately following the spawning season. This study substantially extends the maximum longevity recorded for monacanthids, although males had much shorter lifespans and higher mortality, than females.

Trends in sightings and population structure of white sharks, Carcharodon carcharias, at Seal Island, False Bay, South Africa, and the emigration of subadult female sharks approaching maturity - Adrian M. Hewitt; Alison A. Kock; Anthony J. Booth; Charles L. Griffiths (Environmental Biology of Fishes, 2018)

Drivers of nitrogen transfer in stream food webs across continents - Beth C. Norman; Matt R. Whiles; Sarah M. Collins; Alexander S. Flecker; Steve K. Hamilton; Sherri L. Johnson; Emma J. Rosi; Linda R. Ashkenas; William B. Bowden; Chelsea L. Crenshaw; Todd Crowl; Walter K. Dodds; et al. (Ecology, 2017)
Studies of trophic‐level material and energy transfers are central to ecology. The use of isotopic tracers has now made it possible to measure trophic transfer efficiencies of important nutrients and to better understand how these materials move through food webs. We analyzed data from thirteen 15 N‐ammonium tracer addition experiments to quantify N transfer from basal resources to animals in headwater streams with varying physical, chemical, and biological features. N transfer efficiencies from primary uptake compartments (PUCs; heterotrophic microorganisms and primary producers) to primary consumers was lower (mean 11.5%, range 100%). Total N transferred (as a rate) was greater in streams with open compared to closed canopies and overall N transfer efficiency generally followed a similar pattern, although was not statistically significant. We used principal component analysis to condense a suite of site characteristics into two environmental components. Total N uptake rates among trophic levels were best predicted by the component that was correlated with latitude, DIN:SRP, GPP:ER, and percent canopy cover. N transfer efficiency did not respond consistently to environmental variables. Our results suggest that canopy cover influences N movement through stream food webs because light availability and primary production facilitate N transfer to higher trophic levels.

Physiologically Based Pharmacokinetic Modeling of Transporter-Mediated Hepatic Clearance and Liver Partitioning of OATP and OCT Substrates in Cynomolgus Monkeys - Bridget L. Morse; Jamus G. MacGuire; Anthony M. Marino; Yue Zhao; Maxine Fox; Yueping Zhang; Hong Shen; W. Griffith Humphreys; Punit Marathe; Yurong Lai (The AAPS Journal, 2017)

Multi‐century stasis in C 3 and C 4 grass distributions across the contiguous United States since the industrial revolution - Daniel M. Griffith; Jennifer M. Cotton; Rebecca L. Powell; Nathan D. Sheldon; Christopher J. Still (Journal of Biogeography, 2017)
Aims Understanding the functional response of ecosystems to past global change is crucial to predicting performance in future environments. One sensitive and functionally significant attribute of grassland ecosystems is the percentage of species that use the C 4 versus C 3 photosynthetic pathway. Grasses using C 3 and C 4 pathways are expected to have different responses to many aspects of anthropogenic environmental change that have followed the industrial revolution, including increases in temperature and atmospheric CO 2 , changes to land management and fire regimes, precipitation seasonality, and nitrogen deposition. In spite of dramatic environmental changes over the past 300 years, it is unknown if the C 4 grass percentage in grasslands has shifted. Location Contiguous United States of America. Methods Here, we used stable carbon isotope data (i.e. δ 13 C) from 30 years of soil samples, as well as herbivore tissues that date to 1739 CE , to reconstruct coarse‐grain C 3 and C 4 grass composition in North American grassland sites to compare with modern vegetation. We spatially resampled these three datasets to a shared 100‐km grid, allowing comparison of δ 13 C values at a resolution and extent common for climate model outputs and biogeographical studies. Results At this spatial grain, the bison tissue proxy was superior to the soil proxy because the soils reflect integration of local carbon inputs, whereas bison sample vegetation across landscapes. Bison isotope values indicate that historical grassland photosynthetic‐type composition was similar to modern vegetation. Main conclusions Despite major environmental change, comparing modern plot vegetation data to three centuries of bison δ 13 C data revealed that the biogeographical distribution of C 3 and C 4 grasses has not changed significantly since the 1700s. This is particularly surprising given the expected CO 2 fertilization of C 3 grasses. Our findings highlight the critical importance of capturing the full range of physiological, ecological and demographical processes in biosphere models predicting future climates and ecosystems.

An ecological role for assortative mating under infection? - L. J. Campbell; M. L. Head; L. Wilfert; A. G. F. Griffiths (Conservation Genetics, 2017)

Integrated Gut and Liver Microphysiological Systems for Quantitative In Vitro Pharmacokinetic Studies - Nikolaos Tsamandouras; Wen Li Kelly Chen; Collin D. Edington; Cynthia L. Stokes; Linda G. Griffith; Murat Cirit (The AAPS Journal, 2017)

Ion channelopathies and migraine pathogenesis - Cassie L. Albury; Shani Stuart; Larisa M. Haupt; Lyn R. Griffiths (Molecular Genetics and Genomics, 2017)

Global synthesis of the temperature sensitivity of leaf litter breakdown in streams and rivers - Jennifer J. Follstad Shah; John S. Kominoski; Marcelo Ardón; Walter K. Dodds; Mark O. Gessner; Natalie A. Griffiths; Charles P. Hawkins; Sherri L. Johnson; Antoine Lecerf; Carri J. LeRoy; David W. P. Manning; Amy D. Rosemond; et al. (Global Change Biology, 2017)
Streams and rivers are important conduits of terrestrially derived carbon (C) to atmospheric and marine reservoirs. Leaf litter breakdown rates are expected to increase as water temperatures rise in response to climate change. The magnitude of increase in breakdown rates is uncertain, given differences in litter quality and microbial and detritivore community responses to temperature, factors that can influence the apparent temperature sensitivity of breakdown and the relative proportion of C lost to the atmosphere vs. stored or transported downstream. Here, we synthesized 1025 records of litter breakdown in streams and rivers to quantify its temperature sensitivity, as measured by the activation energy ( E a , in eV ). Temperature sensitivity of litter breakdown varied among twelve plant genera for which E a could be calculated. Higher values of E a were correlated with lower‐quality litter, but these correlations were influenced by a single, N‐fixing genus ( Alnus ). E a values converged when genera were classified into three breakdown rate categories, potentially due to continual water availability in streams and rivers modulating the influence of leaf chemistry on breakdown. Across all data representing 85 plant genera, the E a was 0.34 ± 0.04 eV , or approximately half the value (0.65 eV ) predicted by metabolic theory. Our results indicate that average breakdown rates may increase by 5–21% with a 1–4 °C rise in water temperature, rather than a 10–45% increase expected, according to metabolic theory. Differential warming of tropical and temperate biomes could result in a similar proportional increase in breakdown rates, despite variation in E a values for these regions (0.75 ± 0.13 eV and 0.27 ± 0.05 eV, respectively). The relative proportions of gaseous C loss and organic matter transport downstream should not change with rising temperature given that E a values for breakdown mediated by microbes alone and microbes plus detritivores were similar at the global scale.

Boulder shores in South Africa – a distinct but poorly documented coastal habitat type - L Tucker; CL Griffiths; F Schroeter; HD Vetter (African Journal of Marine Science, 2017)

First report of Laternula elliptica in the Antarctic intertidal zone - Catherine L. Waller; Andy Overall; Elaine M. Fitzcharles; Huw Griffiths (Polar Biology, 2017)

Discordance between morphological and taxonomic diversity: land snails of oceanic archipelagos - Kostas A. Triantis; François Rigal; Christine E. Parent; Robert A. D. Cameron; Bernd Lenzner; Aristeidis Parmakelis; Norine W. Yeung; María R. Alonso; Miguel Ibáñez; António M. de Frias Martins; Dinarte N. F. Teixeira; Owen L. Griffiths; et al. (Journal of Biogeography, 2016)
Aim Morphological and taxonomic diversity are intuitive measures of biological diversity. Previous studies have shown discordance between these measures at large spatial and temporal scales, but the implications of this pattern for the underlying processes are not understood. Using oceanic archipelagos as spatial units, we examine potential links between the morphological and taxonomic diversity of their land snail faunas in a biogeographical framework. Location Eleven major oceanic archipelagos. Methods For each archipelago, we assembled lists of indigenous land snail species, classified by family and genus, with shell height and width for each species (1723 species in total). We used biogeographic and climatic variables as potential predictors of diversity patterns. We employed regression analyses to evaluate (1) whether morphological diversity scales with taxonomic diversity at the species, genus or family level, and (2) whether morphological and taxonomic diversity correlate similarly with biogeographic/climatic factors. We also assessed which taxonomic level contributes most to morphological variation within archipelagos. Results Morphological diversity across archipelagos was strongly related to genus but not species richness. Within archipelagos, morphological variation reflected differences among genera and families but not species. Species richness was best explained by archipelago area, but morphological diversity was not significantly related to any of the physical features of archipelagos. Main conclusions Across archipelagos, species richness and morphological diversity of land snail faunas are decoupled. The relationship between species richness and the available ecological space (captured mainly by area) indicates the prevalence of niche‐based processes while, for morphological diversity, the strong conservatism of morphology at the genus level suggests the presence of diversification‐based limits. Assuming genera effectively reflect diversification, our findings indicate that morphological space on oceanic archipelagos depends primarily on the number of evolutionary units that have colonized and/or diversified through time.

The effect of vigorous running and cycling on serum COMP, lubricin, and femoral cartilage thickness: a pilot study - Harry M. Roberts; Jonathan P. Moore; Claire L. Griffith-McGeever; Matthew B. Fortes; Jeanette M. Thom (European Journal of Applied Physiology, 2016)

Characterization of passive permeability at the blood–tumor barrier in five preclinical models of brain metastases of breast cancer - Chris E. Adkins; Afroz S. Mohammad; Tori B. Terrell-Hall; Emma L. Dolan; Neal Shah; Emily Sechrest; Jessica Griffith; Paul R. Lockman (Clinical & Experimental Metastasis, 2016)

Sex steroid profiles and pair-maintenance behavior of captive wild-caught zebra finches (Taeniopygia guttata) - Nora H. Prior; Kang Nian Yap; Hans H. Adomat; Mark C. Mainwaring; H. Bobby Fokidis; Emma S. Guns; Katherine L. Buchanan; Simon C. Griffith; Kiran K. Soma (Journal of Comparative Physiology A, 2016)

Bottom‐up regulation of malaria population dynamics in mice co‐infected with lung‐migratory nematodes - Emily C. Griffiths; Karen Fairlie‐Clarke; Judith E. Allen; C. Jessica E. Metcalf; Andrea L. Graham (Ecology Letters, 2015)
When and how populations are regulated by bottom up vs. top down processes, and how those processes are affected by co‐occurring species, are poorly characterised across much of ecology. We are especially interested in the community ecology of parasites that must share a host. Here, we quantify how resources and immunity affect parasite propagation in experiments in near‐replicate ‘mesocosms’’ – i.e. mice infected with malaria ( Plasmodium chabaudi ) and nematodes ( Nippostrongylus brasiliensis ). Nematodes suppressed immune responses against malaria, and yet malaria populations were smaller in co‐infected hosts. Further analyses of within‐host epidemiology revealed that nematode co‐infection altered malaria propagation by suppressing target cell availability. This is the first demonstration that bottom‐up resource regulation may have earlier and stronger effects than top‐down immune mechanisms on within‐host community dynamics. Our findings demonstrate the potential power of experimental ecology to disentangle mechanisms of population regulation in complex communities.

Assessing Landscape Change and Processes of Recurrence, Replacement, and Recovery in the Southeastern Coastal Plains, USA - Mark A. Drummond; Michael P. Stier; Roger F. Auch; Janis L. Taylor; Glenn E. Griffith; Jodi L. Riegle; David J. Hester; Christopher E. Soulard; Jamie L. McBeth (Environmental Management, 2015)

Anaerobic digestion of Spirulina sp. and Scenedesmus sp.: a comparison and investigation of the impact of mechanical pre-treatment - A. E. Inglesby; M. J. Griffiths; S. T. L. Harrison; R. P. van Hille (Journal of Applied Phycology, 2015)

Common polygenic variation contributes to risk of migraine in the Norfolk Island population - A. J. Rodriguez-Acevedo; M. A. Ferreira; Miles C. Benton; Melanie A. Carless; Harald H. Goring; Joanne E. Curran; John Blangero; R. A. Lea; L. R. Griffiths (Human Genetics, 2015)

Impact of intra- versus inter-annual snow depth variation on water relations and photosynthesis for two Great Basin Desert shrubs - Michael E. Loik; Alden B. Griffith; Holly Alpert; Amy L. Concilio; Catherine E. Wade; Sharon J. Martinson (Oecologia, 2015)

Assessing the influence of topography and canopy structure on Douglas fir throughfall with LiDAR and empirical data in the Santa Cruz mountains, USA - K. T. Griffith; A. G. Ponette-González; L. M. Curran; K. C. Weathers (Environmental Monitoring and Assessment, 2015)

CMV in the gut: a critical review of CMV detection in the immunocompetent host with colitis - A. L. Goodman; C. D. Murray; J. Watkins; P. D. Griffiths; D. P. Webster (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

You are not always what we think you eat: selective assimilation across multiple whole‐stream isotopic tracer studies - W. K. Dodds; S. M. Collins; S. K. Hamilton; J. L. Tank; S. Johnson; J. R. Webster; K. S. Simon; M. R. Whiles; H. M. Rantala; W. H. McDowell; S. D. Peterson; T. Riis; et al. (Ecology, 2014)
Analyses of 21 15 N stable isotope tracer experiments, designed to examine food web dynamics in streams around the world, indicated that the isotopic composition of food resources assimilated by primary consumers (mostly invertebrates) poorly reflected the presumed food sources. Modeling indicated that consumers assimilated only 33–50% of the N available in sampled food sources such as decomposing leaves, epilithon, and fine particulate detritus over feeding periods of weeks or more. Thus, common methods of sampling food sources consumed by animals in streams do not sufficiently reflect the pool of N they assimilate. Isotope tracer studies, combined with modeling and food separation techniques, can improve estimation of N pools in food sources that are assimilated by consumers. Food web studies that use putative food samples composed of actively cycling (more readily assimilable) and refractory (less assimilable) N fractions may draw erroneous conclusions about diets, N turnover, and trophic linkages of consumers. By extension, food web studies using stoichiometric or natural abundance approaches that rely on an accurate description of food‐source composition could result in errors when an actively cycling pool that is only a fraction of the N pool in sampled food resources is not accounted for.

Interpreting environmental change in coastal Alaska using traditional and scientific ecological knowledge - William G. Ambrose; Lisa M. Clough; Jeffrey C. Johnson; Michael Greenacre; David C. Griffith; Michael L. Carroll; Alex Whiting (Frontiers in Marine Science, 2014)

Plant Conservation Challenges in the Bahama Archipelago - Eric Carey; Lynn Gape; B. Naqqi Manco; Dion Hepburn; Ross L. Smith; Lindy Knowles; David Knowles; Mark Daniels; Michael A. Vincent; Ethan Freid; Brett Jestrow; M. Patrick Griffith; et al. (The Botanical Review, 2014)

Long‐term effects of stock transfers: synergistic introgression of allochthonous genomes in salmonids - J. L. Horreo; G. Machado‐Schiaffino; A. M. Griffiths; D. Bright; J. R. Stevens; E. Garcia‐Vazquez (Journal of Fish Biology, 2014)
The genus Salmo was employed as a model to study introgression of genes between species due to secondary contacts. Seven microsatellite loci, the LDH‐C1 * locus and the 5S ribosomal DNA were studied. Results showed the mutually enhanced introgression of allochthonous genomes into southern European salmonids. This phenomenon appears to go beyond a simple consequence of the altered behaviour of domestic individuals. Invasions of autochthonous genomes by allochthonous genes would be enhanced by human activities such as stock transfers, which would simultaneously promote allochthonous and allospecific (from other species) introgressions in a synergistic process in Atlantic salmon Salmo salar and brown trout Salmo trutta . As a minor result, the data do not support the value of the microsatellite locus SsaD486 as a species‐specific marker.

Large-scale spatial patterns within soft-bottom epibenthic invertebrate assemblages along the west coast of South Africa, based on the Nansen trawl survey - L Lange; CL Griffiths (African Journal of Marine Science, 2014)

Range expansions across ecoregions: interactions of climate change, physiology and genetic diversity - Marc Rius; Susana Clusella‐Trullas; Christopher D. McQuaid; René A. Navarro; Charles L. Griffiths; Conrad A. Matthee; Sophie von der Heyden; Xavier Turon (Global Ecology and Biogeography, 2014)
Aim Climate change is expected to drive range shifts among a wide array of organisms. Non‐indigenous species ( NIS ) provide a unique opportunity to observe the establishment of range boundaries in a way that cannot be directly seen for native species. Recent studies have indicated that climate change facilitates biological invasions at local scales. However, the generality of these effects is unclear, as there is a dearth of comparative studies that assess how rapid environmental change affects species ranges across taxa and biogeographic provinces. Location The S outh A frican coast and other coastlines across the world. Methods We first studied the distribution of shallow‐marine benthic organisms along the S outh A frican coastline and analysed the global distribution of NIS . We then obtained DNA sequence data from a suite of co‐occurring NIS from along the studied coastline and compared these data with available genetic information from other regions of the world. Subsequently, we conducted physiological experiments to assess how thermal tolerance was related to species distribution. Finally, we analysed ship‐based seawater temperature records and compared these with past changes in the range size and abundance of NIS . These records were used to estimate shipping intensity and NIS propagule pressure. Results We found that NIS with a variety of thermal tolerances and distributions have expanded their ranges and increased in abundance as seawater temperature regimes have changed. We found little interannual variation in shipping transport intensity. Most haplotypes of the studied NIS in S outh A frica were shared with other regions. Main conclusions This study provides empirical evidence that NIS , regardless of their thermal tolerance, range size and genetic variability, are expanding their ranges and increasing in abundance. This trend is uncorrelated with levels of human‐mediated NIS transport but concurrent with changes in seawater temperature, which suggests that climate change fosters the spread and abundance of NIS across multiple spatial scales.

Genetic Diversity and Population Structure Among Oat Cultivars and Landraces - G. Montilla-Bascón; J. Sánchez-Martín; N. Rispail; D. Rubiales; L. Mur; T. Langdon; I. Griffiths; C. Howarth; E. Prats (Plant Molecular Biology Reporter, 2013)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Society, marine ecosystems, innovation and change: current states of knowledge in South Africa - C L Moloney; V E Coyne; C L Griffiths; D Scott; M Sowman (African Journal of Marine Science, 2013)

Human-mediated drivers of change — impacts on coastal ecosystems and marine biota of South Africa - A Mead; C L Griffiths; G M Branch; C D McQuaid; L K Blamey; J J Bolton; R J Anderson; F Dufois; M Rouault; P W Froneman; A K Whitfield; L R Harris; et al. (African Journal of Marine Science, 2013)

Deja vu? A second mytilid mussel, Semimytilus algosus , invades South Africa's west coast - K de Greef; C L Griffiths; Z Zeeman (African Journal of Marine Science, 2013)

Efficacy of novel sampling approaches for surveying specialised recreational fisheries - Shane P. Griffiths; Mitchell T. Zischke; Mark L. Tonks; Julian G. Pepperell; Sharon Tickell (Reviews in Fish Biology and Fisheries, 2013)

BDNF and TNF-α polymorphisms in memory - B. S. Yogeetha; L. M. Haupt; K. McKenzie; H. G. Sutherland; R. K. Okolicsyani; R. A. Lea; B. H. Maher; R. C. K. Chan; D. H. K. Shum; L. R. Griffiths (Molecular Biology Reports, 2013)

Turn costs change the value of animal search paths - R. P. Wilson; I. W. Griffiths; P. A. Legg; M. I. Friswell; O. R. Bidder; L. G. Halsey; S. A. Lambertucci; E. L. C. Shepard (Ecology Letters, 2013)
The tortuosity of the track taken by an animal searching for food profoundly affects search efficiency, which should be optimised to maximise net energy gain. Models examining this generally describe movement as a series of straight steps interspaced by turns, and implicitly assume no turn costs. We used both empirical‐ and modelling‐based approaches to show that the energetic costs for turns in both terrestrial and aerial locomotion are substantial, which calls into question the value of conventional movement models such as correlated random walk or Lévy walk for assessing optimum path types. We show how, because straight‐line travel is energetically most efficient, search strategies should favour constrained turn angles, with uninformed foragers continuing in straight lines unless the potential benefits of turning offset the cost.

Agricultural land use alters the seasonality and magnitude of stream metabolism - Natalie A. Griffiths; Jennifer L. Tank; Todd V. Royer; Sarah S. Roley; Emma J. Rosi-Marshall; Matt R. Whiles; Jake J. Beaulieu; Laura T. Johnson (Limnology and Oceanography, 2013)
We present a comprehensive data set of gross primary production (GPP) and ecosystem respiration (ER) in open‐canopy, nutrient‐rich streams draining row‐crop agriculture in the midwestern United States. We used two approaches to characterize temporal and spatial variation in whole‐stream metabolism: continuous measurements in one agricultural stream for 1 yr, and periodic daily measurements in six agricultural streams on six dates spanning summer, autumn, and winter. Continuous measurements revealed high rates of GPP (range: 0.1 to 22.0 g O 2 m −2 d −1 ) and ER (range: −0.9 to −34.8 g O 2 m −2 d −1 ) that varied seasonally with light availability and temperature. GPP and ER were correlated during periods of high autotrophic production, suggesting that autotrophic respiration comprised a large portion of ER; however, the GPP : ER ratio exceeded 1 for only 4% of the year. While there were distinct temporal patterns in metabolism in one agricultural stream, rates of GPP and ER were similar among six streams when assessed via periodic daily measurements, and 26% of all periodic daily measurements were autotrophic with GPP : ER > 1. However, these periodic measurements were collected under baseflow conditions and may have overestimated the extent of autotrophy in agricultural streams. Overall, the open canopy and elevated nutrients of agricultural streams resulted in higher rates of GPP and ER compared with more pristine systems. Estimates of metabolism are needed from underrepresented systems to accurately quantify carbon fluxes from fluvial ecosystems.

Improving the assessment and valuation of climate change impacts for policy and regulatory analysis - Alex L. Marten; Robert E. Kopp; Kate C. Shouse; Charles W. Griffiths; Elke L. Hodson; Elizabeth Kopits; Bryan K. Mignone; Chris Moore; Steve C. Newbold; Stephanie Waldhoff; Ann Wolverton (Climatic Change, 2013)

The first confirmed cases of full albinism in rajid species - R. E. Ball; C. S. Jones; A. Lynghammar; L. R. Noble; A. M. Griffiths (Journal of Fish Biology, 2013)
Three albino skate specimens (Rajidae) were captured from the North Sea and English Channel between 2008 and 2011. Using DNA barcoding ( COI gene) and morphometric analyses, species were identified as a spotted ray Raja montagui , a blonde ray Raja brachyura and a thornback ray Raja clavata . This finding represents the first record of full albinism (a lack of skin and retinal pigmentation) in rajid species.

Effects of trawling on the diets of common demersal fish by‐catch of a tropical prawn trawl fishery - Q. Dell; S. P. Griffiths; M. L. Tonks; W. A. Rochester; M. J. Miller; M. A. Duggan; T. D. van der Velde; R. D. Pillans; G. J. Coman; R. H. Bustamante; D. A. Milton (Journal of Fish Biology, 2013)
The ecological effect of prawn trawling on the benthos of the Gulf of Carpentaria, northern Australia, was investigated by examining stomach contents of common demersal fishes incidentally caught as by‐catch in the fishery. Fishes were collected from high and low fishing intensity sites in three regions based on vessel monitoring system data. The diets of eight species of benthic fish predators were compared between regions and fishing intensities. A regional effect on diet was evident for seven species. Only one generalist species had no significant difference in diet among the three regions. For the comparisons within each region, five predator species had significantly different diet between high and low fishing intensities in at least one region. Across the three regions, high fishing intensity sites had predators that consumed a greater biomass of crustaceans, molluscs and echinoderms. At low fishing intensity sites, predators had diets comprising a greater biomass of cnidarians and teleosts, and a different assemblage of molluscs, crustaceans and fishes. These changes in diet suggest that there may have been a shift in the structure of the benthic community following intensive fishing. Analysis of predator diets is a useful tool to help identify changes in the benthic community composition after exposure to fishing. This study also provided valuable diet information on a range of abundant generalist benthic predators to improve the ecosystem modelling tools needed to support ecosystem‐based fisheries management.

Identification and analysis of an outer-seed-coat-specific promoter from Arabidopsis thaliana - Elahe Esfandiari; Zhaoqing Jin; Ashraf Abdeen; Jonathan S. Griffiths; Tamara L. Western; George W. Haughn (Plant Molecular Biology, 2013)

A possible role for mitochondrial dysfunction in migraine - S. Stuart; L. R. Griffiths (Molecular Genetics and Genomics, 2012)

Carer provisioning rules in an obligate cooperative breeder: prey type, size and delivery rate - L. E. Browning; C. M. Young; J. L. Savage; D. J. F. Russell; H. Barclay; S. C. Griffith; A. F. Russell (Behavioral Ecology and Sociobiology, 2012)

Lipid productivity, settling potential and fatty acid profile of 11 microalgal species grown under nitrogen replete and limited conditions - Melinda J. Griffiths; Robert P. van Hille; Susan T. L. Harrison (Journal of Applied Phycology, 2012)

A suggested new bacteriophage genus: “Viunalikevirus” - Evelien M. Adriaenssens; Hans-Wolfgang Ackermann; Hany Anany; Bob Blasdel; Ian F. Connerton; David Goulding; Mansel W. Griffiths; Steven P. Hooton; Elizabeth M. Kutter; Andrew M. Kropinski; Ju-Hoon Lee; Martine Maes; et al. (Archives of Virology, 2012)
We suggest a bacteriophage genus, “Viunalikevirus”, as a new genus within the family Myoviridae . To date, this genus includes seven sequenced members: Salmonella phages ViI, SFP10 and ΦSH19; Escherichia phages CBA120 and PhaxI; Shigella phage phiSboM-AG3; and Dickeya phage LIMEstone1. Their shared myovirus morphology, with comparable head sizes and tail dimensions, and genome organization are considered distinguishing features. They appear to have conserved regulatory sequences, a horizontally acquired tRNA set and the probable substitution of an alternate base for thymine in the DNA. A close examination of the tail spike region in the DNA revealed four distinct tail spike proteins, an arrangement which might lead to the umbrella-like structures of the tails visible on electron micrographs. These properties set the suggested genus apart from the recently ratified subfamily Tevenvirinae , although a significant evolutionary relationship can be observed.

Changes in the choice of colorectal cancer screening tests in primary care settings from 7,845 prospectively collected surveys - Martin C. S. Wong; George K. John; Hoyee W. Hirai; Thomas Y. T. Lam; Arthur K. C. Luk; Jessica Y. L. Ching; Simon S. M. Ng; Francis K. L. Chan; Sian M. Griffiths; Joseph J. Y. Sung (Cancer Causes & Control, 2012)

Genome‐wide analysis of longevity in nutrient‐deprived Saccharomyces cerevisiae reveals importance of recycling in maintaining cell viability - Hazel M. Davey; Emma J. M. Cross; Christopher, L. Davey; Konstantinos Gkargkas; Daniela Delneri; David C. Hoyle; Stephen G. Oliver; Douglas B. Kell; Gareth W. Griffith (Environmental Microbiology, 2012)
Summary Although typically cosseted in the laboratory with constant temperatures and plentiful nutrients, microbes are frequently exposed to much more stressful conditions in their natural environments where survival and competitive fitness depend upon both growth rate when conditions are favourable and on persistence in a viable and recoverable state when they are not. In order to determine the role of genetic heterogeneity in environmental fitness we present a novel approach that combines the power of fluorescence‐activated cell sorting with barcode microarray analysis and apply this to determining the importance of every gene in the Saccharomyces cerevisiae genome in a high‐throughput, genome‐wide fitness screen. We have grown > 6000 heterozygous mutants together and exposed them to a starvation stress before using fluorescence‐activated cell sorting to identify and isolate those individual cells that have not survived the stress applied. Barcode array analysis of the sorted and total populations reveals the importance of cellular recycling mechanisms (autophagy, pexophagy and ribosome breakdown) in maintaining cell viability during starvation and provides compelling evidence for an important role for fatty acid degradation in maintaining viability. In addition, we have developed a semi‐batch fermentor system that is a more realistic model of environmental fitness than either batch or chemostat culture. Barcode array analysis revealed that arginine biosynthesis was important for fitness in semi‐batch culture and modelling of this regime showed that rapid emergence from lag phase led to greatly increased fitness. One hundred and twenty‐five strains with deletions in unclassified proteins were identified as being over‐represented in the sorted fraction, while 27 unclassified proteins caused a haploinsufficient phenotype in semi‐batch culture. These methods thus provide a screen to identifying other genes and pathways that have a role in maintaining cell viability.

Development of an eight gene expression profile implicating human breast tumours of all grade - P. N. Gabrovska; R. A. Smith; T. Tiang; S. R. Weinstein; L. M. Haupt; L. R. Griffiths (Molecular Biology Reports, 2012)

Evidence for evolutionary distinctiveness of a newly discovered population of sooglossid frogs on Praslin Island, Seychelles - Michele L. Taylor; Nancy Bunbury; Lindsay Chong-Seng; Naomi Doak; Samit Kundu; Richard A. Griffiths; Jim J. Groombridge (Conservation Genetics, 2012)

Building genetic networks using relatedness information: a novel approach for the estimation of dispersal and characterization of group structure in social animals - LEE ANN ROLLINS; LUCY E. BROWNING; CLARE E. HOLLELEY; JAMES L. SAVAGE; ANDREW F. RUSSELL; SIMON C. GRIFFITH (Molecular Ecology, 2012)
Natal dispersal is an important life history trait driving variation in individual fitness, and therefore, a proper understanding of the factors underlying dispersal behaviour is critical to many fields including population dynamics, behavioural ecology and conservation biology. However, individual dispersal patterns remain difficult to quantify despite many years of research using direct and indirect methods. Here, we quantify dispersal in a single intensively studied population of the cooperatively breeding chestnut‐crowned babbler ( Pomatostomus ruficeps ) using genetic networks created from the combination of pairwise relatedness data and social networking methods and compare this to dispersal estimates from re‐sighting data. This novel approach not only identifies movements between social groups within our study sites but also provides an estimation of immigration rates of individuals originating outside the study site. Both genetic and re‐sighting data indicated that dispersal was strongly female biased, but the magnitude of dispersal estimates was much greater using genetic data. This suggests that many previous studies relying on mark–recapture data may have significantly underestimated dispersal. An analysis of spatial genetic structure within the sampled population also supports the idea that females are more dispersive, with females having no structure beyond the bounds of their own social group, while male genetic structure expands for 750 m from their social group. Although the genetic network approach we have used is an excellent tool for visualizing the social and genetic microstructure of social animals and identifying dispersers, our results also indicate the importance of applying them in parallel with behavioural and life history data.

Revealing the scale of marine bioinvasions in developing regions: a South African re-assessment - A. Mead; J. T. Carlton; C. L. Griffiths; M. Rius (Biological Invasions, 2011)

United States Pharmacopeia Safety Evaluation of Spirulina - Robin J. Marles; Marilyn L. Barrett; Joanne Barnes; Mary L. Chavez; Paula Gardiner; Richard Ko; Gail B. Mahady; Tieraona Low Dog; Nandakumara D. Sarma; Gabriel I. Giancaspro; Maged Sharaf; James Griffiths (Critical Reviews in Food Science and Nutrition, 2011)

Remote sensing classification of grass seed cropping practices in western Oregon - George W. Mueller-Warrant; Gerald W. Whittaker; Stephen M. Griffith; Gary M. Banowetz; Bruce D. Dugger; Tiffany S. Garcia; Guillermo Giannico; Kathryn L. Boyer; Brenda C. McComb (International Journal of Remote Sensing, 2011)

Microsatellite standardization and evaluation of genotyping error in a large multi-partner research programme for conservation of Atlantic salmon (Salmo salar L.) - J. S. Ellis; J. Gilbey; A. Armstrong; T. Balstad; E. Cauwelier; C. Cherbonnel; S. Consuegra; J. Coughlan; T. F. Cross; W. Crozier; E. Dillane; D. Ensing; et al. (Genetica, 2011)

Benzonatate Ingestion Reported to the National Poison Center Database System (NPDS) - Mark L. Winter; Henry A. Spiller; Jill R. K. Griffith (Journal of Medical Toxicology, 2010)

Isolation and characterization of 12 polymorphic tetranucleotide microsatellite loci in the apostlebird (Struthidea cinerea) - L. A. Rollins; C. E. Holleley; J. Wright; A. F. Russell; S. C. Griffith (Conservation Genetics Resources, 2010)

Deposition of Atlantic salmon Salmo salar carcasses in a Scottish upland catchment - K. L. Williams; S. W. Griffiths; S. McKelvey; J. D. Armstrong (Journal of Fish Biology, 2010)
Radio telemetry was utilized to track 38 Atlantic salmon Salmo salar across space and time during and following their spawning run on the Conon system, Scotland. The data collected were used to assess the proportion of S. salar able to migrate successfully from an upland oligotrophic area of the catchment and the distribution of the carcasses of those fish that remained. Of these fish, 35% successfully migrated from the study area after the spawning period. The fish that remained were distributed approximately equally between riverine and lacustrine areas, but with a strong tendency to accumulate in regions of relatively slow water flows.

Soil nutrients are not responsible for arrested succession in disturbed coastal dune forest - L. J. Boyes; M. E. Griffiths; A. D. Manson; M. J. Lawes (Plant Ecology, 2010)

Following the chain to elusive anglers - Shane P. Griffiths; Kenneth H. Pollock; Jeremy M. Lyle; Julian G. Pepperell; Mark L. Tonks; William Sawynok (Fish and Fisheries, 2010)
Obtaining reliable estimates of important parameters from recreational fisheries is problematic but critical for stock assessment and effective resource management. Sampling methodologies based on traditional design‐based sampling theory, is inadequate in obtaining representative catch and effort data, social or demographical characterization, or fisher behaviour from small hard‐to‐reach components within recreational fisheries (e.g. specialized sport fisheries) that may account for the majority of the catch for some species. A model‐based approach to sampling is necessary. Researchers in other disciplines including epidemiology and social sciences routinely survey rare or ‘hidden’ populations within the general community by penetration of social networks rather than by interception of individuals. We encourage fisheries researchers to rethink survey designs and consider the social elements of recreational fishing. Employing chain‐referral methods, such as respondent‐driven sampling (RDS), may be a statistically robust and cost‐effective option for sampling elusive sub‐elements within recreational fisheries. Chain‐referral sampling methodology is outlined and an example of a complemented ‘RDS‐recapture’ survey design is introduced as a cost‐effective application to estimating total catch in recreational fisheries.

Population-level resource selection by sympatric brown and American black bears in Alaska - Jerrold L. Belant; Brad Griffith; Yingte Zhang; Erich H. Follmann; Layne G. Adams (Polar Biology, 2010)

Patient preferences and National Health Service costs: a cost-consequences analysis of cancer genetic services - Gethin L. Griffith; Rhiannon Tudor Edwards; J. Mark G. Williams; Jonathon Gray; Val Morrison; Clare Wilkinson; Jim Turner; Barbara France; Paul Bennett (Familial Cancer, 2009)

Lipid productivity as a key characteristic for choosing algal species for biodiesel production - Melinda J. Griffiths; Susan T. L. Harrison (Journal of Applied Phycology, 2009)

Response of juvenile Atlantic salmon, Salmo salar , to the introduction of salmon carcasses in upland streams - K. L. WILLIAMS; S. W. GRIFFITHS; K. H. NISLOW; S. McKELVEY; J. D. ARMSTRONG (Fisheries Management and Ecology, 2009)
The role of nutrients in the production of Atlantic salmon, Salmo salar L., in oligotrophic upland catchments is poorly understood. Atlantic salmon carcasses were introduced to 12 upland streams in the River Conon catchment, Scotland, UK, to assess potential nutrient limitation and evaluate a potential role for migratory Atlantic salmon in nutrient import. The objective was to test the hypothesis that nutrient supplementation would increase juvenile Atlantic salmon biomass. Streams received one of six treatment levels up to a maximum of one carcass per 15 m 2 of wetted area with duplicates at each level, and study areas were sampled to measure salmon biomass in treated and reference reaches. There was a significant positive relationship between treatment addition level and response of juvenile salmon biomass. At higher carcass addition levels, salmon biomass in treatment sections was approximately twice that in paired reference sections. The results are discussed in the light of management methods in upland regions and the likely role of cultural oligotrophication in suppressing current levels of salmon production.

Caffeine withdrawal, acute effects, tolerance, and absence of net beneficial effects of chronic administration: cerebral blood flow velocity, quantitative EEG, and subjective effects - Stacey C. Sigmon; Ronald I. Herning; Warren Better; Jean L. Cadet; Roland R. Griffiths (Psychopharmacology, 2009)

Geographic patterns of non-carpeted floor dust loading in Syracuse, New York (USA) homes - D. L. Johnson; A. Hunt; D. A. Griffith; J. M. Hager; J. Brooks; H. StellaLevinsohn; A. Lanciki; R. Lucci; D. Prokhorova; S. L. Blount (Environmental Geochemistry and Health, 2009)

Bycatch in a tropical schooling – penaeid fishery and comparisons with a related, specialised trawl regime - Q. DELL; D. T. BREWER; S. P. GRIFFITHS; D. S. HEALES; M. L. TONKS (Fisheries Management and Ecology, 2009)
The bycatch in a tropical Australian banana prawn, Penaeus merguiensis (de Man), fishery is described and contrasted with the closely related tiger prawn, Penaeus semisulcatus De Haan and Penaeus esculentus Haswell, fishery. Most of the similarity between banana prawn fishery catches was accounted for by three teleost species constituting 51.4% of the total bycatch weight. The bycatch assemblage structure of this fishery was significantly different ( P 0.05) from the adjoining tiger prawn fishery. The banana prawn fishery had a higher mean bycatch catch rate from shorter duration trawls, but lower estimated total annual bycatch (1502 t yr −1 ) than the longer duration trawls of the tiger prawn fishery (20 073 t yr −1 ). This study provides new data for quantifying bycatch and improving the accuracy of quantitative risk assessments currently being used to demonstrate sustainability of bycatch populations. The information will be incorporated into collaborative development of a long‐term monitoring programme.

Synthesis and pharmacological characterization of [125I]MRS1898, a high-affinity, selective radioligand for the rat A3 adenosine receptor - Zhan-Guo Gao; Bao Teng; Haitao Wu; Bhalchandra V. Joshi; Gary L. Griffiths; Kenneth A. Jacobson (Purinergic Signalling, 2009)

Global GPS data analysis at the National Geodetic Survey - William G. Kass; Robert L. Dulaney; Jake Griffiths; Stephen Hilla; Jim Ray; James Rohde (Journal of Geodesy, 2009)

Seasonal decline in reproductive performance varies with colony size in the fairy martin, Petrochelidon ariel - Michael J. L. Magrath; Peter Santema; Karen M. Bouwman; Dušan M. Brinkhuizen; Simon C. Griffith; Naomi E. Langmore (Behavioral Ecology and Sociobiology, 2009)

Linkage mapping of CVD risk traits in the isolated Norfolk Island population - C. Bellis; H. C. Cox; T. D. Dyer; J. C. Charlesworth; K. N. Begley; S. Quinlan; R. A. Lea; S. C. Heath; J. Blangero; L. R. Griffiths (Human Genetics, 2008)

Risk remaining from fine particle contaminants after vacuum cleaning of hard floor surfaces - Andrew Hunt; David L. Johnson; J. Brooks; Daniel A. Griffith (Environmental Geochemistry and Health, 2008)

Genes driving potato tuber initiation and growth: identification based on transcriptional changes using the POCI array - Bjorn Kloosterman; David De Koeyer; Rebecca Griffiths; Barry Flinn; Burkhard Steuernagel; Uwe Scholz; Sophia Sonnewald; Uwe Sonnewald; Glenn J. Bryan; Salomé Prat; Zsófia Bánfalvi; John P. Hammond; et al. (Functional & Integrative Genomics, 2008)

The Use of Routine Process Capability for the Determination of Process Parameter Criticality in Small-molecule API Synthesis - Kevin D. Seibert; Shanthi Sethuraman; Jerry D. Mitchell; Kristi L. Griffiths; Bernard McGarvey (Journal of Pharmaceutical Innovation, 2008)

Functional resilience of soil microbial communities depends on both soil structure and microbial community composition - B. S. Griffiths; P. D. Hallett; H. L. Kuan; A. S. Gregory; C. W. Watts; A. P. Whitmore (Biology and Fertility of Soils, 2008)

Competition between brown trout and Atlantic salmon parr over pool refuges during rapid dewatering - L. Stradmeyer; J. Höjesjö; S. W. Griffiths; D. J. Gilvear; J. D. Armstrong (Journal of Fish Biology, 2008)
Variations in distributions and behaviours of Atlantic salmon Salmo salar in allopatry (homogeneous) and in sympatry with brown trout Salmo trutta (mixed) were observed before, during and after 2 day periods of dewatering in a large glass‐sided indoor stream at densities typical of Scottish upland streams. Brown trout utilized pools more than Atlantic salmon at normal flows and in both species the majority of fishes moved into pools during dewatering. There was no significant effect of brown trout, which was the more dominant species, on the overall ability of Atlantic salmon to use pool habitat as a refuge during dewatering. Within mixed and homogeneous groups, average feeding levels decreased during dewatering. The highest ranking fish, which was always a brown trout in mixed groups, predominantly monopolized the pool and other individuals in pools adopted a more cryptic, stationary behaviour. Dewatering effectively increased local population density with the result that dominance status became much more important in maintaining food intake, and polarization between the top ranking fish and others increased. During the first day of dewatering, there was extreme behavioural polarization such that the dominant fish exhibited most aggression and least feeding within the group. Among dominant fish on the second day of dewatering, aggression had largely abated and feeding had returned to pretreatment levels despite the reduced average feeding within the group. The main difference between mixed and homogeneous groups was in the behaviour of the most dominant Atlantic salmon, which was near‐despotic in allopatry and subordinate to brown trout in sympatry.

Implications of life history for genetic structure and migration rates of southern African coastal invertebrates: planktonic, abbreviated and direct development - P. R. Teske; I. Papadopoulos; G. I. Zardi; C. D. McQuaid; M. T. Edkins; C. L. Griffiths; N. P. Barker (Marine Biology, 2007)

Geography of asbestos contamination near the World Trade Center site - William C. Thayer; Daniel A. Griffith; Gary L. Diamond (Stochastic Environmental Research and Risk Assessment, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

The invasion and subsequent die-off of Mytilus galloprovincialis in Langebaan Lagoon, South Africa: effects on natural communities - T. B. Robinson; C. L. Griffiths; G. M. Branch; A. Govender (Marine Biology, 2007)

Exploration of Ellsworth Subglacial Lake: a concept paper on the development, organisation and execution of an experiment to explore, measure and sample the environment of a West Antarctic subglacial lake - M.J. Siegert; A. Behar; M. Bentley; D. Blake; S. Bowden; P. Christoffersen; C. Cockell; H. Corr; D. C. Cullen; H. Edwards; A. Ellery; C. Ellis-Evans; et al. (Reviews in Environmental Science and Bio/Technology, 2007)

Modelling neural informational propagation and functional auditory sensory memory with temporal multi-scale operators - Maja Šerman; Nikola Šerman; Niall J. L. Griffith (Journal of Computational Neuroscience, 2007)

Isolation of viral haemorrhagic septicaemia virus from mummichog, stickleback, striped bass and brown trout in eastern Canada - N Gagné; A‐M MacKinnon; L Boston; B Souter; M Cook‐Versloot; S Griffiths; G Olivier (Journal of Fish Diseases, 2007)
Viral haemorrhagic septicaemia virus (VHSV) was isolated from mortalities occurring in populations of mummichog, Fundulus heteroclitus , stickleback, Gasterosteus aculeatus aculeatus , brown trout, Salmo trutta , and striped bass, Morone saxatilis , in New Brunswick and Nova Scotia, Canada. The isolated viral strains produced a cytopathic effect on the epithelioma papillosum cyprini cell line. Serum neutralization indicated the virus was VHSV and sequencing identified the rhabdovirus isolates as the North American strain of VHSV. Phylogenetic analysis indicated that the isolates are closely related and form a distinguishable subgroup of North American type VHSV. To our knowledge, this is the first report of VHSV in mummichog and striped bass.

Histone deacetylase inhibitors enhance Ad5-TRAIL killing of TRAIL-resistant prostate tumor cells through increased caspase-2 activity - Rebecca L. VanOosten; James K. Earel; Thomas S. Griffith (Apoptosis, 2007)

Is sex-specific mass gain in Cory’s shearwaters Calonectris diomedea related to begging and steroid hormone expression? - Petra Quillfeldt; Inga Träger; Kate Griffiths; Katherine L. Buchanan; Juan F. Masello (Behavioral Ecology and Sociobiology, 2007)

Crop pathogens and other Fusarium species associated with Austrostipa aristiglumis - A. R. Bentley; T. Petrovic; S. P. Griffiths; L. W. Burgess; B. A. Summerell (Australasian Plant Pathology, 2007)

Comparison and Verification of Bacterial Water Quality Indicator Measurement Methods Using Ambient Coastal Water Samples - John F. Griffith; Larissa A. Aumand; Ioannice M. Lee; Charles D. Mcgee; Laila L. Othman; Kerry J. Ritter; Kathy O. Walker; Stephen B. Weisberg (Environmental Monitoring and Assessment, 2006)

Targeted disruption of mouse Coch provides functional evidence that DFNA9 hearing loss is not a COCH haploinsufficiency disorder - Tomoko Makishima; Clara I. Rodriguez; Nahid G. Robertson; Cynthia C. Morton; Colin L. Stewart; Andrew J. Griffith (Human Genetics, 2005)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

Low gene flow but high genetic diversity in the threatened Mallorcan midwife toad Alytes muletensis - F. J. L. KRAAIJEVELD‐SMIT; T. J. C. BEEBEE; R. A. GRIFFITHS; R. D. MOORE; L. SCHLEY (Molecular Ecology, 2005)
We investigated fine‐scale genetic structuring in the rare and vulnerable Mallorcan midwife toad Alytes muletensis using eight polymorphic microsatellite markers. The current range of this amphibian is restricted to some 19 sites of which six are derived from reintroductions, all located in the mountain ranges of Mallorca. We sampled tadpoles from 14 pools covering 10 natural sites and two reintroduction sites for microsatellite DNA analyses. Relatively high levels of genetic variation were found in most pools ( H E = 0.38–0.71, allelic richness = 2.6–6.2). Only at one pool has the population recently gone through a bottleneck. Dispersal between pools in different torrents does not occur whereas downstream dispersal between pools within the same torrent does happen at low frequencies. This occasional exchange of individuals does not lead to neighbouring pools in the same torrent being panmictic. This can be concluded because all F ST values (0.12–0.53) differ significantly from zero and structure analyses identified neighbouring pools as separate populations. Furthermore, assignment and migration tests showed little exchange between neighbouring pools. If upstream locations or complete torrents go extinct, they are unlikely to be recolonized naturally. For conservation purposes, reintroductions of tadpoles to sites where local extinctions have occurred may therefore be advisable.

Change in mean temperature as a predictor of extreme temperature change in the Asia–Pacific region - G. M. Griffiths; L. E. Chambers; M. R. Haylock; M. J. Manton; N. Nicholls; H.‐J. Baek; Y. Choi; P. M. Della‐Marta; A. Gosai; N. Iga; R. Lata; V. Laurent; et al. (International Journal of Climatology, 2005)
Trends (1961–2003) in daily maximum and minimum temperatures, extremes and variance were found to be spatially coherent across the Asia–Pacific region. The majority of stations exhibited significant trends: increases in mean maximum and mean minimum temperature, decreases in cold nights and cool days, and increases in warm nights. No station showed a significant increase in cold days or cold nights, but a few sites showed significant decreases in hot days and warm nights. Significant decreases were observed in both maximum and minimum temperature standard deviation in China, Korea and some stations in Japan (probably reflecting urbanization effects), but also for some Thailand and coastal Australian sites. The South Pacific convergence zone (SPCZ) region between Fiji and the Solomon Islands showed a significant increase in maximum temperature variability. Correlations between mean temperature and the frequency of extreme temperatures were strongest in the tropical Pacific Ocean from French Polynesia to Papua New Guinea, Malaysia, the Philippines, Thailand and southern Japan. Correlations were weaker at continental or higher latitude locations, which may partly reflect urbanization. For non‐urban stations, the dominant distribution change for both maximum and minimum temperature involved a change in the mean, impacting on one or both extremes, with no change in standard deviation. This occurred from French Polynesia to Papua New Guinea (except for maximum temperature changes near the SPCZ), in Malaysia, the Philippines, and several outlying Japanese islands. For urbanized stations the dominant change was a change in the mean and variance, impacting on one or both extremes. This result was particularly evident for minimum temperature. The results presented here, for non‐urban tropical and maritime locations in the Asia–Pacific region, support the hypothesis that changes in mean temperature may be used to predict changes in extreme temperatures. At urbanized or higher latitude locations, changes in variance should be incorporated. Copyright © 2005 Royal Meteorological Society.

Infrared observations and numerical modelling of grassland fires in the Northern Territory, Australia - T. L. Clark; M. J. Reeder; M. Griffiths; D. Packham; N. Krusel (Meteorology and Atmospheric Physics, 2005)

Fluvial system response to Late Devensian (Weichselian) aridity, Baston, Lincolnshire, England - Rebecca M. Briant; G. Russell Coope; Richard C. Preece; David H. Keen; Steve Boreham; Huw I. Griffiths; Mary B. Seddon; Philip L. Gibbard (Journal of Quaternary Science, 2004)
Little is known about the impact of Late Devensian (Weichselian) aridity on lowland British landscapes, largely because they lack the widespread coversand deposits of the adjacent continent. The concentration of large interformational ice‐wedge casts in the upper part of many Devensian fluvial sequences suggests that fluvial activity may have decreased considerably during this time. The development of optically stimulated luminescence (OSL) dating enables this period of ice‐wedge cast formation to be constrained for the first time in eastern England, where a marked horizon of ice‐wedge casts is found between two distinctive dateable facies associations. Contrasts between this horizon and adjacent sediments show clear changes in environment and fluvial system behaviour in response to changing water supply, in line with palaeontological evidence. In addition to providing chronological control on the period of ice‐wedge formation, the study shows good agreement of the radiocarbon and OSL dating techniques during the Middle and Late Devensian, with direct comparison of these techniques beyond 15 000 yr for the first time in Britain. It is suggested that aridity during the Late Devensian forced a significant decrease in fluvial activity compared with preceding and following periods, initiating a system with low peak flows and widespread permafrost development. Copyright © 2004 John Wiley & Sons, Ltd.

Thermophilic bacterial DNA polymerases with reverse-transcriptase activity - Kate Griffiths; Harini Shandilya; Elizabeth K. Flynn; Mekbib Astatke; Po-Jen Shih; Jun E. Lee; Gary F. Gerard; Moreland D. Gibbs; Peter L. Bergquist (Extremophiles, 2004)

Influence of wave exposure on South African mussel beds and their associated infaunal communities - W. Hammond; C. L. Griffiths (Marine Biology, 2004)

Longitudinal stratification of gait economy in young boys and girls: the locomotion energy and growth study - Jennifer L. Caputo; Daniel J. Keefer; Ian S. Craig; Kelly B. Griffith; Mary Beth Akins; Gareth E. Griffith; Gary S. Krahenbuhl; Philip E. Martin; Don W. Morgan; Wayland Tseh (European Journal of Applied Physiology, 2004)

The relationship between dominance behaviour and growth as a function of habitat stability and community complexity: a test using salmon and trout - J. Höjesjö; L. Stradmeyer; J. Armstrong; S. Griffiths (Journal of Fish Biology, 2003)
When two or more species coexist, there is often a differentiation in habitat use, temporally and/or spatially, either due to differences in habitat preference or in competitive abilities. Trout and salmon, for example, often coexist in the same river but whereas trout generally occupy pools, salmon are more often found in riffles. This segregation might be due to differences in habitat preference but could also occur as a consequence of salmon being out‐competed by trout from the pools. Food in riffle sections has been found to be relatively unpredictable in time and space whereas pools are believed to be more spatially predictable. It should therefore be easier for fish to monopolize food resources in pools than riffles and hence the importance of dominance might be most significant for pool‐dwelling fish. In agreement with this theory, dominance have been shown to increase growth rate in brown trout whereas no such relationship has been found in salmon. This experiment was therefore designed to detect whether the relationship between growth rate and dominance in salmon might vary depending on whether they co‐exist with trout or are free to select pool habitat with no trout present. The experiment was carried out in an indoor stream landscaped with both pools and riffles and equipped with a feeding system designed to mimic natural spatial and temporal variation in food supply. This set up allowed us to perform controlled behavioural observations under near‐natural conditions. The results from this study will be presented and discussed.

Behavioural strategies for species co‐existence during environmental extremes: competition between trout and salmon parr during dewatering - L. Stradmeyer; J. Höjesjö; J. Armstrong; S. Griffiths (Journal of Fish Biology, 2003)
Competition between species of animals can be predicted to be intense under extreme environmental conditions during which niche overlap increases. Fluvial aquatic systems fluctuate naturally across a broad range of time‐scales. Land management activities impose further extreme fluctuations, particularly when water is abstracted for irrigation during summer. This study focused on the interaction between Atlantic salmon and brown trout parr during acute dewatering events. Brown trout are known to compete strongly for pool habitat whereas salmon can coexist by using riffle areas during normal flows. It is not known, however, how competition between the species affects their behavioural responses to extreme low flows when riffle areas decrease. Replicated groups of salmon were held in allopatry and sympatry with trout in sections of a large indoor stream, each of which was landscaped into riffles and pools. Space use and behaviours of the fish were recorded by direct visual observations and a network of Passive Integrated Transponder detectors. Here we report the response of the fish to dewatering and consider the system as a model for natural and forced responses of communities to environmental extremes.

Development and Evaluation of a Macroinvertebrate Biotic Integrity Index (MBII) for Regionally Assessing Mid-Atlantic Highlands Streams - DONALD J. KLEMM; KAREN A. BLOCKSOM; FLORENCE A. FULK; ALAN T. HERLIHY; ROBERT M. HUGHES; PHILIP R. KAUFMANN; DAVID V. PECK; JOHN L. STODDARD; WILLIAM T. THOENY; MICHAEL B. GRIFFITH; WAYNE S. DAVIS (Environmental Management, 2003)

Assessment of PCB Congener Analytical Methods: Do They Meet Risk Assessment Needs? - N. L. Judd; W. C. Griffith; D. A. Kalman; E. M. Faustman (Archives of Environmental Contamination and Toxicology, 2003)

Alternative Strategies for PCB Risk Reduction from Contaminated Seafood: Options for Children as Susceptible Populations - N. L. Judd; W. C. Griffith; G. M. Ylitalo; E. M. Faustman (Bulletin of Environmental Contamination and Toxicology, 2002)

Expression of a Truncated Brca1 Protein Delays Lactational Mammary Development in Transgenic Mice - Melissa A. Brown; Hans Nicolai; Kathy Howe; Toyomasa Katagiri; El-Nasir Lalani; Kaylene J. Simpson; Nathan W. Manning; Andrew Deans; Phil Chen; Kum Kum Khanna; Mas Rina Wati; Beatrice L. Griffiths; et al. (Transgenic Research, 2002)

Development of STS markers closely linked to the Ppd-H1 photoperiod response gene of barley (Hordeum vulgare L.) - L. Decousset; S. Griffiths; R. P. Dunford; N. Pratchett; D. A. Laurie (Theoretical and Applied Genetics, 2000)

DNA sex identification in the three‐spined stickleback - R. Griffiths; K. L. Orr; A. Adam; I. Barber (Journal of Fish Biology, 2000)
Two sex linked DNA markers are isolated in the three‐spined stickleback Gasterosteus aculeatus and a sex identification test is developed.

Genetic Distances Among North American, British, and West African House Fly Populations (Musca domestica L.) - E. S. Krafsur; N. L. Bryant; J. G. Marquez; N. T. Griffiths (Biochemical Genetics, 2000)

Genetic dissection of collagen-induced arthritis in Chromosome 10 quantitative trait locus speed congenic rats: evidence for more than one regulatory locus and sex influences - Bina Joe; Elaine F. Remmers; David E. Dobbins; Jennifer L. Salstrom; Takefumi Furuya; Svetlana Dracheva; Pércio S. Gulko; Grant W. Cannon; Marie M. Griffiths; Ronald L. Wilder (Immunogenetics, 2000)

Verifying Inventory Predictions of Animal Methane Emissions with Meteorological Measurements - O. T. Denmead; R. Leuning; D. W. T. Griffith; I. M. Jamie; M. B. Esler; L. A. Harper; J. R. Freney (Boundary-Layer Meteorology, 2000)

Caffeine withdrawal increases cerebral blood flow velocity and alters quantitative electroencephalography (EEG) activity - H. E. Jones; R. I. Herning; J. L. Cadet; R. R. Griffiths (Psychopharmacology, 2000)

Identification of a new quantitative trait locus on Chromosome 7 controlling disease severity of collagen-induced arthritis in rats - Svetlana V. Dracheva; Elaine F. Remmers; Pércio S. Gulko; Yutaka Kawahito; Ryan E. Longman; Van R. Reese; Grant W. Cannon; Marie M. Griffiths; R. L. Wilder (Immunogenetics, 1999)

A genetic linkage map of rat Chromosome 15 derived from five F 2 crosses - Jennifer S. Shepard; Elaine F. Remmers; Stephen Chen; Lisa Chang; Yutaka Kawahito; Pércio S. Gulko; Bina Joe; Ryan E. Longman; Svetlana Dracheva; Lynn Ge; Jianping Wang; Van R. Reese; et al. (Mammalian Genome, 1999)

A genetic linkage map of rat chromosome 20 derived from five F 2 crosses - Y. Kawahito; Elaine F. Remmers; R. L. Wilder; Ryan E. Longman; Pércio S. Gulko; Jianping Wang; Stephen Chen; Lisa Chang; V. R. Reese; Svetlana Dracheva; Lynn Ge; Jean H. Hoffman; et al. (Immunogenetics, 1998)

Gene symbol: COL11A1 Disease: Marshall Syndrome - M. H. Meisler; A. J. Griffith; M. Warman; G. Tiller; L. K. Sprunger (Human Genetics, 1998)

Regulation of gene expression by endogenous ABA in tomato plants - Elizabeth A. Bray; Amybeth Cohen; Áine L. Plant; Meena S. Moses; Ryozo Imai; Allen Griffiths (Acta Physiologiae Plantarum, 1997)

A secondary effect of transformation in Rhizobium leguminosarum transgenic for Bacillus thuringiensis subspecies tenebrionisδ-endotoxin (cryIIIA) genes - G. Giddings; L. Mytton; M. Griffiths; A. McCarthy; C. Morgan; L. Skøt (Theoretical and Applied Genetics, 1997)

Characterisation of Escherichia coli K-12 mutants defective in formate-dependent nitrite reduction: essential roles for hemN and the menFDBCE operon - K. Tyson; R. Metheringham; L. Griffiths; J. Cole (Archives of Microbiology, 1997)

Tenidap inhibits 5-lipoxygenase product formation in vitro, but this activity is not observed in three animal models - T. J. Carty; F. J. Sweeney; R. J. Griffiths; J. D. Eskra; M. J. Ernest; J. S. Pillar; J. D. Cheng; L. D. Loose; P. A. Joseph; P. P. Pazoles; P. F. Moore; A. Nagahisa; et al. (Inflammation Research, 1997)

Middle Pleistocene deposits at Frog Hall Pit, Stretton‐on-Dunsmore, Warwickshire, English Midlands, and their implications for the age of the type Wolstonian - D. H. Keen; G. R. Coope; R. L. Jones; M. H. Field; H. I. Griffiths; S. G. Lewis; D. Q. Bowen (Journal of Quaternary Science, 1997)

Middle Pleistocene deposits at Frog Hall Pit, Stretton-on-Dunsmore, Warwickshire, English Midlands, and their implications for the age of the type Wolstonian - D. H. Keen; G. R. Coope; R. L. Jones; M. H. Field; H. I. Griffiths; S. G. Lewis; D. Q. Bowen (Journal of Quaternary Science, 1997)

Lack of redox control of the anaerobically-induced nirB + gene of Escherichia coli K-12 - L. Griffiths; J. A. Cole (Archives of Microbiology, 1987)

Mouse cytomegalovirus is infectious for rats and alters lymphocyte subsets and spleen cell proliferation - C. B. Smith; L. S. Wei; Marie Griffiths (Archives of Virology, 1986)